Pigment composition, photosensitive composition and organic el display device

JP2025021576APending Publication Date: 2025-02-14TORAY INDUSTRIES INC

Patent Information

Application Number
JP2023125366
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0020】 本発明の顔料組成物によれば、ハーフトーン加工により一括形成された画素分割層およびスペーサー層の形成膜厚が厚い場合であっても、画素分割層およびスペーサー層形成時における基板の中央部に配置された発光画素の正常な点灯を維持しつつ、該基板の端部に配置された発光画素の非点灯が抑制された有機EL表示装置を得ることが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021576000001_ABST
    Figure 2025021576000001_ABST
Patent Text Reader

Abstract

To provide a pigment composition enabling to obtain OLED display devices in which non-lighting of light-emitting pixels located at an edge of a substrate is suppressed while maintaining normal lighting of light-emitting pixels located at a center of the substrate during formation of a pixel division layer and spacer layer, even if a thickness of the pixel division layer and spacer layer formed in a batch by the halftone process is thick.SOLUTION: A pigment composition contains (a) a pigment having -NHCO- and / or -COO- groups and a triphenodioxazine skeleton in a molecule, and (b) a compound represented by a Formula (1) and / or a Formula (2).SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pigment composition, a photosensitive composition, and an organic electroluminescence display device. [Background technology]

[0002] In recent years, various organic electroluminescence (EL) display devices have been developed, and by adopting a structure that does not include a thick polarizing plate that was conventionally placed on the front part of the panel, it is expected that the loss of brightness caused by the polarizing plate will be eliminated, and power consumption will be reduced and the product life of the display device will be improved. In order to separate each light-emitting pixel in the light-emitting element of the organic EL display device, a pattern that functions as an insulating layer called a pixel division layer or pixel definition layer is arranged. In order to replace the function of the polarizing plate, it is necessary to give the layer a function to suppress the reflection of external light such as sunlight, and a technology that gives the pixel division layer light-shielding properties by adding a color material with light-shielding properties has attracted attention. In addition, in order to improve visibility and increase the value of the display device, it is necessary to improve the light-shielding properties of the pixel division layer.

[0003] Incidentally, in order to significantly improve the yield rate during panel production, a technique is known in which, when pattern-depositing an emitting layer on the openings of the pixel division layer, a convex spacer layer is formed on a part of the surface of the pixel division layer to reduce the contact area between the deposition mask and the pixel division layer and suppress the occurrence of defects. As a method for forming the pixel division layer and the spacer layer, a technique (halftone processing) is known in which the pixel division layer and the spacer layer are formed together by a photolithography method including an exposure step of irradiating exposure light including at least near ultraviolet light through a halftone exposure mask having a fully transparent part, a semi-transparent part, and a shielding part in its surface. The halftone processing can significantly reduce the process cost compared to a two-layer processing in which a spacer layer is further laminated and formed after the formation of the pixel division layer, and can economically manufacture an organic EL display device.

[0004] As a material for forming a light-shielding pixel division layer and a spacer layer at the same time, a positive-type photosensitive composition having excellent halftone processability and combining high exposure sensitivity and high storage stability is disclosed in Patent Document 1. The positive-type photosensitive composition uses a triphenodioxazine-based pigment or a perylene-based pigment having a benzimidazole skeleton, which are organic pigments having high near-infrared transmittance, light-shielding properties, heat resistance, and insulation properties. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2022 / 270182 Summary of the Invention [Problem to be solved by the invention]

[0006] However, when an organic EL display device having a pixel division layer (e.g., 2.5 μm or more thick) and a spacer layer (e.g., 1.5 μm or more thick) with enhanced light-shielding properties is driven using the positive photosensitive composition disclosed in Patent Document 1, all of the light-emitting pixels arranged in the central region of the substrate when the pixel division layer and the spacer layer are formed light up normally, but at least some of the light-emitting pixels arranged in the edge region of the substrate do not light up. On the other hand, if the size of the substrate is increased so that the pixel division layer and the spacer layer are formed collectively to eliminate the need to arrange light-emitting pixels at the edge of the substrate, and the edge of the substrate is cut and discarded, this leads to a large loss of an area that can be effectively used, which is economically disadvantageous. In view of the above, in an organic EL display device having pixel division layers and spacer layers that have been formed to have thicker thicknesses through half-tone processing to enhance light-blocking properties, there is a strong demand for a technology that maintains normal lighting of light-emitting pixels located in the center of the substrate when the pixel division layers and spacer layers are formed, while suppressing non-lighting of light-emitting pixels located at the ends of the substrate. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention has the following configuration. [1] A pigment composition containing: (a) a pigment having an -NHCO- group and / or a -COO- group and a triphenodioxazine skeleton in its molecule; and (b) a compound represented by formula (1) and / or a compound represented by formula (2).

[0008] [ka]

[0009] In formula (1), -R 1 and -SO 2 NHR 2 R 3 represents a substituent bonded to a carbon atom constituting a benzene ring. 1 and m 2 are integers, each independently representing 0 to 2. 1 and m 2 The sum of is 1 or 2. 1 -SO 3 H or -SO 3 - Represents R 2 R represents a single bond or an alkylene group having 1 to 3 carbon atoms. 3 -SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.

[0010] [ka]

[0011] In formula (2), M represents V=O, Ti=O or Zn. 4 , -SO 2 NHR 5 R 6, -Br and -Cl represent a substituent or an atom bonded to a carbon atom constituting a benzene ring. n 1 and n 2 are integers, each independently representing 0 to 2. 3 is an integer from 0 to 14. 4 is an integer ranging from 0 to 5. n 1 and 2 and 3 and 4 The sum of is 1 to 16, and n 1 and 2 The sum is 0 to 2. n 1 and 2 When the sum of is 0, M is Zn and n 3 is 8 to 14. 4 -SO 3 H or -SO 3 - Represents R 5 R represents a single bond or an alkylene group having 1 to 3 carbon atoms. 6 -SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents. [2] The pigment composition according to [1], wherein the component (b) contains a compound represented by formula (28) and / or a compound represented by formula (29).

[0012] [ka]

[0013] In formula (28), -R 51 represents a substituent bonded to a carbon atom constituting a benzene ring. 3 is an integer, either 1 or 2. 51 -SO 3 H or -SO 3 - Represents.

[0014] [ka]

[0015] In formula (29), -R 52 , -Br and -Cl represent substituents or atoms bonded to the carbon atoms constituting the benzene ring. 5 and 6 and 7 The sum of n is 1 to 16. 5 is an integer from 0 to 2. 6 is an integer from 0 to 14. 7 is an integer from 0 to 5. 5 When is 0, n 6 is 8 to 14. 52 -SO 3 H or -SO 3 - Represents. [3] The pigment composition according to [1] or [2], wherein the content of Cu atoms in the solid content of the pigment composition as determined by inductively coupled plasma mass spectrometry (ICP-MS) is 100 mass ppm or less. [4] The pigment composition according to any one of [1] to [3], further comprising (c) a pigment having a benzimidazole skeleton and a perylene skeleton in the molecule. [5] The pigment composition according to any one of claims [1] to [4], further comprising a (d) resin, the (d) resin comprising a resin having a repeating unit represented by formula (43) and / or a resin having a repeating unit represented by formula (44).

[0016] [ka]

[0017] (In formula (43), R 69 represents a phenyl group substituted with one hydroxyl group, an unsubstituted phenyl group, or a hydrogen atom. p is an integer of 0 to 2. * represents a bonding site.

[0018] [ka]

[0019] (In formula (44), R 70 R represents a hydrogen atom or a methyl group. 71 represents a single bond or a -COO- group. * represents a bonding site.) [6] A photosensitive composition comprising the pigment composition according to any one of [1] to [5] above, (d) a resin, (e) an organic solvent, and (f) a photosensitizer. [7] The photosensitive composition according to [6], wherein the component (f) contains a photoacid generator and has positive photosensitivity. [8] An organic electroluminescence display device comprising a pixel dividing layer and a spacer layer, the pixel dividing layer and the spacer layer containing a cured product of the photosensitive composition according to [6] or [7]. Effect of the Invention

[0020] According to the pigment composition of the present invention, even when the pixel division layer and the spacer layer formed collectively by halftone processing have a large thickness, it is possible to obtain an organic EL display device in which the light-emitting pixels arranged in the center of the substrate are maintained in normal lighting during the formation of the pixel division layer and the spacer layer, while non-lighting of the light-emitting pixels arranged at the ends of the substrate is suppressed. [Brief description of the drawings]

[0021] [Figure 1] 4 is a schematic diagram showing the positional relationship between a central region and an end region in a substrate surface when a pixel division layer and a spacer layer are formed. FIG. [Diagram 2] FIG. 1 is a schematic diagram showing an example in which a plurality of organic EL display devices are manufactured on one substrate. [Diagram 3] 1 is an image of a cross section of a substrate for evaluating a required minimum exposure dose obtained in Example 1, observed with a scanning electron microscope (SEM). [Figure 4] The process for producing an organic EL display device in all of the examples and comparative examples includes a process for forming a pixel dividing layer and a spacer layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be described in detail below. A numerical range expressed using "~" means a range including the numerical values ​​described before and after "~" as the lower and upper limits. The pixel division layer means a pixel division layer provided in an organic EL display device, and does not include the black matrix of an organic EL display device and a liquid crystal display device. The black matrix here means a light-shielding layer arranged on a color filter substrate arranged on the light extraction side of the display device to separate color filters such as red, green, and blue. Visible light means light in a wavelength range of 380 nm or more and less than 780 nm, and near ultraviolet light means light in a wavelength range of 200 nm or more and less than 380 nm. Light-shielding means a function of reducing the intensity of transmitted light relative to the intensity of light incident perpendicularly to the cured film, and light-shielding property means the degree of blocking visible light. Transmittance means light transmittance.

[0023] The solid content means the ratio (mass %) of the components excluding water and organic solvent in the pigment composition or positive photosensitive composition. The pigment composition means a composition in which the components excluding water and organic solvent contain a plurality of compounds including at least a pigment, and the solid content is 70 to 100 mass %. In this specification, the resin means a compound having a weight average molecular weight (Mw) of 1000 or more, having a repeating unit containing an organic group, and having three or more repeating units in one molecule. The weight average molecular weight (Mw) is a value obtained by analyzing by gel permeation chromatography (GPC) using tetrahydrofuran as a carrier and converting the value using a calibration curve of standard polystyrene.

[0024] The present inventors have conducted intensive research focusing in particular on pigments among the various components contained in the photosensitive composition for forming the pixel dividing layer and the spacer layer, and as a result, have found that a pigment composition containing a triphenodioxazine pigment having a specific structure and a phthalocyanine derivative having a specific structure has an exceptionally remarkable effect in solving the above-mentioned problems.

[0025] That is, the pigment composition according to the first embodiment of the present invention is (a) a pigment having an -NHCO- group and / or a -COO- group and a triphenodioxazine skeleton in the molecule, and (b) a pigment composition containing a compound represented by formula (1) and / or a compound represented by formula (2).

[0026] [ka]

[0027] In formula (1), -R 1 and -SO 2 NHR 2 R 3 represents a substituent bonded to a carbon atom constituting a benzene ring. 1 and m 2 are integers, each independently representing 0 to 2. 1 and m 2 The sum of is 1 or 2. 1 -SO 3 H or -SO 3 - Represents R 2 R represents a single bond or an alkylene group having 1 to 3 carbon atoms. 3 -SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.

[0028] [ka]

[0029] In formula (2), M represents V=O, Ti=O or Zn. 4 , -SO 2 NHR 5 R 6, -Br and -Cl represent a substituent or an atom bonded to a carbon atom constituting a benzene ring. n 1 and n 2 are integers, each independently representing 0 to 2. 3 is an integer from 0 to 14. 4 is an integer ranging from 0 to 5. n 1 and 2 and 3 and 4 The sum of is 1 to 16, and n 1 and 2 The sum is 0 to 2. n 1 and 2 When the sum of is 0, M is Zn and n 3 is 8 to 14. 4 -SO 3 H or -SO 3 - Represents R 5 R represents a single bond or an alkylene group having 1 to 3 carbon atoms. 6 -SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.

[0030] Even when the pixel division layer and spacer layer formed collectively by halftone processing have a large thickness, the pigment composition of the present invention has the effect of suppressing non-illumination of light-emitting pixels arranged at the edge of the substrate (hereinafter sometimes abbreviated as "non-illumination of edges") while maintaining normal illumination of light-emitting pixels arranged at the center of the substrate at the time of forming the pixel division layer and spacer layer, thereby enhancing the value of the organic EL display device.

[0031] Here, the thick film thickness means that the pixel division layer has a thickness of 2.5 μm or more and the spacer layer has a thickness of 1.5 μm or more (i.e., the total thickness of the pixel division layer and the spacer layer is 4.0 μm or more). By making the pixel division layer have a thickness of 2.5 μm or more, high light blocking properties can be obtained, improving visibility, and the value of the finally obtained organic EL display device can be increased. In addition, by making the spacer layer have a thickness of 1.5 μm or more, chipping or damage to the light emitting element can be prevented when the light emitting layer is pattern-deposited on the opening of the pixel division layer, and the yield rate during panel production can be improved. In order to improve the halftone processability described later, the total film thickness of the pixel division layer and the spacer layer is preferably 10.0 μm or less. The central part of the substrate when the pixel division layer and the spacer layer are formed here means the region shown in 1 in FIG. 1. The edge part of the substrate when the pixel division layer and the spacer layer are formed means the region shown in 2 in FIG. 1.

[0032] In Figure 1, W 1 is the length of the long side of the board, W 2 W represents the length of the short side of the board. 3 W 1 W represents the length of the end that is 20% of the 4 W 2 This represents the length of the end portion that is 20% of the

[0033] The technical effect of suppressing non-illumination at the edge brings about economically advantageous value even when manufacturing multiple organic EL display devices on one substrate. An example of an embodiment is shown in FIG. 2. In FIG. 2, one area surrounded by a dashed line represents an area where one organic EL display device is arranged, and after a total of 16 units are manufactured on one substrate, they are cut into small pieces. The present invention can reduce the defect rate of the 12 organic EL display devices arranged at the edge.

[0034] The pigment composition of the present invention contains (a) a pigment having an -NHCO- group and / or -COO- group and a triphendioxazine skeleton in the molecule (hereinafter, sometimes referred to as component (a)) as an essential component. The -NHCO- group here means a group represented by formula (3), and the -COO- group means a group represented by formula (4). The triphendioxazine skeleton means a skeleton represented by formula (5). The triphendioxazine skeleton is also called a triphendioxazine skeleton. Therefore, in this specification, a pigment having a triphenodioxazine skeleton in the molecule is defined as being synonymous with a pigment having a triphendioxazine skeleton in the molecule. Component (a) is a pigment that exhibits a reddish or bluish dark purple color.

[0035] [ka]

[0036] In formula (3) and formula (4), * represents a binding site.

[0037] [ka]

[0038] Component (a) provides excellent halftone processability to the photosensitive composition described below and also provides light-shielding properties to the pixel division layer. The excellent halftone processability here means that when a pixel division layer having an opening of a desired opening width and a spacer layer are formed at the same time, development residues that may occur on the surface of the opening of the pixel division layer are suppressed. In addition, component (a) has both high light-shielding properties in the visible light region and high transmittance in the near-infrared region, allowing exposure alignment using a near-infrared camera to be easily performed, and the yield of panel production can be improved by increasing the positional accuracy of the exposure mask relative to the substrate.

[0039] As the component (a), in terms of improving halftone processability and light blocking properties, the pigment represented by formula (6) and / or the pigment represented by formula (7) is preferred. That is, the pigment composition of the present invention preferably contains, as component (a), a pigment represented by formula (6) and / or a pigment represented by formula (7).

[0040] [ka]

[0041] In formula (6), R 7 and R 8 R each independently represents an alkyl group having 1 to 8 carbon atoms. 9 and R 10 R each independently represents an alkyl group having 1 to 8 carbon atoms, a phenyl group substituted with an alkyl group having 1 to 8 carbon atoms, or an unsubstituted phenyl group. 11 and R 12 R each independently represents -NH- or an oxygen atom. 13 , R 14 , R 15 , R 16 , R 17 , R 18 , R 19 , R 20 , R 21 and R 22 R each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. 23 and R 24 represents -CONH-.

[0042] In addition, in formula (6), the carbon atom of the carbonyl group of the -CONH- group may be bonded to a carbon atom constituting the triphenodioxazine skeleton, or may be bonded to a carbon atom constituting the phenyl group which may have a substituent.

[0043] [ka]

[0044] In formula (7), R 25 and R 26 R each independently represents a hydrogen atom or an alkyl group having 1 to 8 carbon atoms. 27 and R 28 R each independently represents an alkyl group having 1 to 8 carbon atoms, a phenyl group substituted with an alkyl group having 1 to 8 carbon atoms, or an unsubstituted phenyl group. 29 and R 30 each independently represents -NH- or an oxygen atom.

[0045] In order to suppress non-lighting at the end portions, it is more preferable that the component (a) contains a pigment represented by formula (8) and / or a pigment represented by formula (9). From the same viewpoint, the pigment represented by formula (8) is even more preferable. That is, the pigment composition of the present invention more preferably contains, as component (a), a pigment represented by formula (8) and / or a pigment represented by formula (9).

[0046] [ka]

[0047] In formula (8), R 31 , R 32 , R 33 and R 34 each independently represents an alkyl group having 1 to 4 carbon atoms. R 35 , R 36 , R 37 , R 38 , R 39 , R 40 , R 41 , R 42 , R 43 and R 44 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, or an alkoxy group having 1 to 4 carbon atoms. R 45 and R 46 represents -CONH-. In formula (8), the carbon atom of the carbonyl group of the -CONH- group may be bonded to a carbon atom constituting the triphenodioxazine skeleton, or may be bonded to a carbon atom constituting the phenyl group which may have a substituent.

[0048] [ka]

[0049] In formula (9), R 47 , R 48 , R 49 and R 50 each independently represents an alkyl group having 1 to 4 carbon atoms.

[0050] Specific examples of the component (a) include a pigment represented by formula (10), a pigment represented by formula (11), a pigment represented by formula (12), a pigment represented by formula (13), a pigment represented by formula (14), a pigment represented by formula (15), a pigment represented by formula (16), a pigment represented by formula (17), a pigment represented by formula (18), a pigment represented by formula (19), a pigment represented by formula (20), and a pigment represented by formula (21). The component (a) may be one type, or may be a mixture of two or more types of pigment or mixed crystal pigment.

[0051] [ka]

[0052] [ka]

[0053] [ka]

[0054] [ka]

[0055] The method for synthesizing component (a) is not particularly limited, and can refer to, for example, the method described in French Patent Application Publication No. 1269107. In addition, a method for synthesizing the pigment represented by formula (10) is given as a specific example, and a method for synthesizing component (a) that can be preferably employed in the present invention is described below.

[0056] In the first step, ammonium hydroxide is added, preferably 2 to 3 mol, per mol of chloranil in a solvent and stirred. The mixture is reacted for 1 to 6 hours at a liquid temperature of 30 to 100°C to obtain a product in which two of the four chlorine atoms in chloranil are converted to primary amino groups, i.e., 2,5-diamino-3,6-dichloro-1,4-benzoquinone, and the product is separated by filtration. As the solvent, for example, 2-methoxy-1-methylethyl acetate, 2-methoxyethyl acetate, or 3-methoxybutyl acetate can be used.

[0057] In the second step, the above-mentioned product is added to acetic anhydride, and the mixture is reacted with acetanilide by stirring at a liquid temperature of 10 to 60°C for 1 to 24 hours, and the intermediate represented by formula (22) is obtained and separated by filtration. In order to increase the reaction rate, an organic acid such as benzenesulfonic acid or p-toluenesulfonic acid may be added. The product obtained in the first step or the intermediate obtained in the second step may be a commercially available product manufactured by Tokyo Chemical Industry Co., Ltd.

[0058] [ka]

[0059] In the third step, a compound represented by formula (23) is added as an aromatic primary amine, preferably 2 to 3 mol, to 1 mol of the intermediate represented by formula (22) in a solvent and stirred. The mixture is reacted by stirring for 5 to 10 hours at a liquid temperature of 70 to 130°C to obtain a triphenodioxazine precursor represented by formula (24). In order to increase the reaction rate, a tertiary amine such as triethylamine, tripropylamine, or tributylamine may be used. Examples of the solvent include dichlorobenzene, trichlorobenzene, 3-methoxytoluene, 4-methoxytoluene, methylphenyl ether, ethylphenyl ether, nonane, decane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, and 1,3-dipropyl-2-imidazolidinone.

[0060] [ka]

[0061] In the fourth step, an oxidizing agent is added as a ring-closing assistant, and the mixture is stirred for 5 to 10 hours at a liquid temperature of preferably 140 to 200°C to perform ring closure of the triphenodioxazine precursor represented by formula (24), and the compound represented by formula (10) having an oxazine ring formed is obtained as a pigment crude. If necessary, a recrystallization operation may be performed to control the shape of the primary particles. Examples of the oxidizing agent include benzenesulfonyl chloride, p-toluenesulfonyl chloride, m-nitrobenzenesulfonyl chloride, p-nitrobenzenesulfonyl chloride, p-chlorobenzenesulfonyl chloride, and p-toluenesulfonic acid.

[0062] In the fifth step, the mixture is cooled to 100°C or less, and then repeatedly washed with water and filtered, and if necessary, purified with a solvent such as ethanol, butanol, or acetone to increase the purity of component (a).The mixture is then heated or dried under reduced pressure, and then pulverized into fine particles by a dry grinding process to obtain the dark purple pigment represented by formula (10).

[0063] Based on the above synthesis method, various pigments belonging to component (a) can be obtained. For example, by using 3-amino-9-ethylcarbazole as the aromatic primary amine in the third step, the pigment represented by formula (13) can be obtained. In addition, by using sodium hydroxide instead of ammonium hydroxide in the first step to generate a compound having a carboxylic acid ester bond, i.e., 2,5-dichloro-3,6-dihydroxy-p-benzoquinone, and then by ring-closing the compound using 3-amino-9-hexylcarbazole as the aromatic primary amine in the third step, the pigment represented by formula (15) can be obtained.

[0064] In addition, by changing the third step and subsequent steps in the above-mentioned synthesis method to the following method, for example, a pigment represented by formula (16) can be obtained, as will be specifically described below.

[0065] In the third step, 2-ethoxy-4-aminobenzoic acid is added, preferably 2 to 3 mol, to 1 mol of the intermediate represented by the above formula (22) in a solvent, and the mixture is reacted by stirring for 5 to 10 hours at a liquid temperature of 70 to 130° C. to obtain a triphenodioxazine precursor represented by formula (25). Examples of the solvent include dichlorobenzene, trichlorobenzene, 3-methoxytoluene, 4-methoxytoluene, methylphenyl ether, ethylphenyl ether, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, and 1,3-dipropyl-2-imidazolidinone.

[0066] [ka]

[0067] In the fourth step, an oxidizing agent is added and the mixture is stirred for 5 to 10 hours, preferably at a liquid temperature of 140 to 200° C., to close the ring of the triphenodioxazine precursor represented by formula (23) to form an oxazine ring, thereby obtaining a compound represented by formula (26). As the oxidizing agent, the same group of compounds as the above-mentioned oxidizing agents can be used.

[0068] [ka]

[0069] Next, in the fifth step, 1 mol of a compound represented by formula (26), which is a dicarboxylic acid, is added to 10 to 15 mol of thionyl chloride, and the mixture is stirred for 5 to 10 hours, preferably at a liquid temperature of 40 to 70°C, to obtain an acid chloride in which the hydroxyl groups are converted to chlorine atoms. Furthermore, 2 to 3 mol of aminobenzene is added as an aromatic primary amine, and the mixture is stirred for 5 to 10 hours. After cooling to 100°C or less, the mixture is washed with water and filtered to obtain a wet cake. Next, the mixture is heated or dried under reduced pressure, and then pulverized by dry grinding to obtain a dark purple pigment represented by formula (16).

[0070] Based on the above synthesis method, various pigments belonging to component (a) can be obtained. For example, if 4-ethylaniline is used as the aromatic primary amine in the fifth step, the pigment represented by formula (17) can be obtained.

[0071] In addition to component (a), the dry grinding treatment for producing components (b) and (c) described below, as well as the pigment composition of the present invention, can be carried out using a ball mill and / or a jet mill. An example of a ball mill is BM-15 (manufactured by Eisin Co., Ltd.). An example of a jet mill is Nano Jet Mizer (registered trademark) (manufactured by Aisin Nano Technologies Co., Ltd.) and fluidized bed opposed jet mill 100AFG (manufactured by Hosokawa Micron Co., Ltd.).

[0072] The pigment composition of the present invention contains, as an essential component, (b) a compound represented by formula (1) and / or a compound represented by formula (2) (hereinafter, sometimes referred to as component (b)). Component (b) exerts a synergistic effect with component (a) in the finally obtained organic EL display device, which exhibits a unique effect of suppressing non-lighting of light-emitting pixels arranged in the edge regions of the substrate during the formation of a pixel dividing layer and a spacer layer.

[0073] [ka]

[0074] In formula (1), -R 1 and -SO 2 NHR 2 R 3 represents a substituent bonded to a carbon atom constituting a benzene ring. 1 and m 2 are integers, each independently representing 0 to 2. 1 and m 2 The sum of is 1 or 2. 1 -SO 3 H or -SO 3 - Represents R 2 R represents a single bond or an alkylene group having 1 to 3 carbon atoms. 3 -SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.

[0075] [ka]

[0076] In formula (2), M represents V=O, Ti=O or Zn. 4 , -SO 2 NHR 5 R 6 , -Br and -Cl represent a substituent or an atom bonded to a carbon atom constituting a benzene ring. n 1 and n 2 are integers, each independently representing 0 to 2. 3 is an integer from 0 to 14. 4 is an integer ranging from 0 to 5. n 1 and 2 and 3 and 4 The sum of is 1 to 16, and n 1 and2 The sum is 0 to 2. n 1 and 2 When the sum of is 0, M is Zn and n 3 is 8 to 14. 4 -SO 3 H or -SO 3 - Represents R 5 R represents a single bond or an alkylene group having 1 to 3 carbon atoms. 6 -SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.

[0077] The carbon atoms constituting the benzene ring here refer to 16 carbon atoms at specific positions in one metal-free phthalocyanine skeleton, more specifically, the carbon atoms marked with position numbers 1 to 16 in formula (27). In formula (1), the bonding positions of the substituents bonded to the carbon atoms constituting the benzene ring are not particularly limited. That is, based on the technical common sense of a person skilled in the art, formula (1) includes both a case where the bonding position to the carbon atom is a single compound and a case where the bonding position to the carbon atom is a mixture of multiple compounds different from each other. The same viewpoint is also applied to the formulas representing the chemical structures of the (b) components other than the compound represented by formula (1).

[0078] [ka]

[0079] In order to suppress non-lighting at the end portions, the component (b) preferably contains a compound represented by formula (28) and / or a compound represented by formula (29). It is more preferable that the component (b) contains at least a compound represented by formula (29). That is, the pigment composition of the present invention preferably contains, as component (b), a compound represented by formula (28) and / or a compound represented by formula (29).

[0080] [ka]

[0081] In formula (28), -R 51 represents a substituent bonded to a carbon atom constituting a benzene ring. 3 is an integer, either 1 or 2. 51 -SO 3 H or -SO 3 - Represents.

[0082] [ka]

[0083] In formula (29), -R 52 , -Br and -Cl represent substituents or atoms bonded to the carbon atoms constituting the benzene ring. 5 and 6 and 7 The sum of n is 1 to 16. 5 is an integer from 0 to 2. 6 is an integer from 0 to 14. 7 is an integer from 0 to 5. 5 When is 0, n 6 is 8 to 14. 52 -SO 3 H or -SO 3 - Represents.

[0084] Specific examples of the component (b) include a compound represented by formula (30), a compound represented by formula (31), a compound represented by formula (32), a compound represented by formula (33), a compound represented by formula (34), a compound represented by formula (35), a compound represented by formula (36), and a compound represented by formula (37). The component (b) may be one type, or a mixture or mixed crystal of two or more types.

[0085] [ka]

[0086] [ka]

[0087] The method for obtaining the component (b) is not particularly limited, but for example, it can be easily synthesized by using metal-free phthalocyanine, vanadyl phthalocyanine, titanyl phthalocyanine or zinc phthalocyanine as a starting material and introducing a desired substituent or atom. Here, vanadyl phthalocyanine is synonymous with oxovanadium phthalocyanine, and titanyl phthalocyanine is synonymous with oxotitanium phthalocyanine. These phthalocyanine compounds are available as high-purity products purified by sublimation from Sigma-Aldrich and Tokyo Chemical Industry Co., Ltd. In addition, pigmented fine-grained metal-free phthalocyanine, i.e., CI Pigment Blue 16, can also be used, and any crystal form such as α-type, β-type, γ-type, or η-type can be used.

[0088] (b) Component (1), -R 1 The compound having a substituent represented by the following formula can be obtained, for example, by the following method.

[0089] Metal-free phthalocyanine is dissolved in 10-50% by mass fuming sulfuric acid or 70-90% by mass concentrated sulfuric acid as a starting material, and the liquid temperature is adjusted to a range of 30-80°C and stirred for 3-8 hours to proceed with the sulfonation reaction, and a sulfo group is introduced into the benzene ring of the metal-free phthalocyanine skeleton. By setting the liquid temperature at 30°C or higher, the remaining unreacted part of the starting material can be suppressed, and by setting the liquid temperature at 80°C or lower, the decomposition of the starting material can be suppressed, and the purity of the sulfonated product can be increased. Next, the starting material is dropped into water, preferably ice water, of a mass 100 times or more the mass of which is greater than that of the starting material, to obtain a blue-green slurry. After washing with an alcohol such as ethanol, the mixture is repeatedly washed with water and filtered until the residual amount of sulfate ions measured by ion chromatography (hereinafter sometimes referred to as "IC") is preferably less than 50 mass ppm, to obtain a wet cake, which is dried at 60-80°C under reduced pressure for 10 hours or more, and then pulverized by a dry grinding process. The number of sulfo groups introduced per molecule of the target product and their distribution can be controlled by the liquid temperature, reaction time, etc. according to the concentration of fuming sulfuric acid, and the reaction conditions may be one-stage or two-stage or more. By-products with three or more sulfo groups introduced have high solubility in water, so they can be removed together with the sulfate ions mentioned above by adjusting the number of washings with water. Liquid chromatography mass spectrometry (LC-MS) and time-of-flight secondary ion mass spectrometry (TOF-SIMS) can be used to determine the reaction end point and identify the chemical structure. In addition, the purity of the compound with a specific range of sulfo groups introduced can be increased by performing a purification process using silica gel chromatography as necessary.

[0090] By the above operations, a mixture of the compound represented by the formula (30) and the compound represented by the formula (31), which corresponds to the compound represented by the formula (1), is obtained. In the same manner as described above, for example, vanadyl phthalocyanine, titanyl phthalocyanine or zinc phthalocyanine is used as a starting material instead of metal-free phthalocyanine, where M is V=O (vanadyl), Ti=O (titanyl) or Zn, and R 4 -SO 3 H, n 1 Compounds in which is 1 or 2 are obtained.

[0091] On the other hand, the component (b), -SO 2 NHR 2 R 3 The compound having a substituent represented by the following formula can be obtained, for example, by the following method.

[0092] Metal-free phthalocyanine is dissolved in chlorosulfonic acid as a starting material, thionyl chloride is added dropwise, and the mixture is stirred at a liquid temperature of 10 to 30°C for 1 to 10 hours. The mixture is then dropped into water, preferably ice water, at a mass 10 times or more the mass of the starting material to obtain a blue-green slurry, which is filtered and washed to obtain a wet cake containing metal-free phthalocyanine sulfochloride. 3-aminopropionic acid is added as a monoamine to a 5 to 30% aqueous sodium hydroxide solution, and the wet cake containing metal-free phthalocyanine sulfochloride is further added and stirred at a liquid temperature of 0 to 5°C for 1 to 3 hours, and further stirred at a liquid temperature of 20 to 70°C for 1 to 5 hours to allow the reaction to proceed. If necessary, the reaction can be allowed to proceed gently at a low liquid temperature to suppress the by-production of sulfo groups and increase the purity of the product into which only sulfonamide groups are introduced. Next, while continuing to stir, a 5 to 30% aqueous hydrochloric acid solution is added dropwise until the pH reaches 2 to 4, and the mixture is washed with an alcohol such as ethanol. After that, the mixture is repeatedly washed with water and filtered until the amount of remaining chloride ions as determined by IC falls below preferably 50 mass ppm, to obtain a wet cake, which is dried at 60 to 80°C under reduced pressure for 10 hours or more and then pulverized by a dry grinding process.

[0093] By the above operations, a mixture of the compound represented by formula (32) and the compound represented by formula (33) can be obtained. In a similar manner, for example, by using o-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid, or p-aminobenzenesulfonic acid as a monoamine instead of 3-aminopropionic acid, R 2 is a single bond, and R 3 But -SO 3 The compound obtained is a phenyl group substituted with one H.

[0094] The compound having -Br and -Cl in formula (2), which is component (b), can be obtained, for example, by the following method.

[0095] The starting material, zinc phthalocyanine, is mixed with bromine, sulfuryl chloride, sodium chloride, and aluminum chloride, and heated at 120 to 150°C for 10 to 50 hours to introduce bromine and chlorine atoms. The mixture is then poured into water with a mass 100 times or more that of the starting material to obtain a green slurry, which is then filtered and washed with water. After washing with ethanol, the mixture is repeatedly washed with water and filtered until the residual amounts of chlorine ions and bromine ions, as determined by IC, are preferably below 50 mass ppm, respectively, to obtain a wet cake, which is then dried at 60 to 80°C under reduced pressure for 10 hours or more and then pulverized by dry grinding.

[0096] The above operations produce a compound represented by formula (37). The number of bromine and / or chlorine atoms introduced per molecule of the target product can be easily controlled by the formulation amounts of bromine and sulfuryl chloride, which are halogenating agents. In the same manner as described above, for example, vanadyl phthalocyanine or titanyl phthalocyanine can be used as the starting material instead of zinc phthalocyanine, and a compound represented by formula (2) where M is V=O (vanadyl) or Ti=O (titanyl) and n 3 is 1 to 14, and n 4 After the introduction of the bromine atom and / or chlorine atom, the compound having -R 4 and / or -SO 2 NHR 5 R 6 A substituent represented by the following formula may be further introduced.

[0097] In order to enhance the effect of component (b) in suppressing non-lighting of the end portion, the pigment composition of the present invention preferably has a Cu atom content of 100 mass ppm or less, more preferably 50 mass ppm or less in the pigment composition. The Cu content here means the content determined by inductively coupled plasma mass spectrometry (ICP-MS). That is, the pigment composition of the present invention preferably has a Cu atom content of 100 mass ppm or less in the solid content of the pigment composition as determined by inductively coupled plasma mass spectrometry (ICP-MS). Examples of the form in which Cu atoms are present include copper ions derived from the raw material for synthesizing component (b) and compounds having a copper phthalocyanine skeleton.

[0098] In order to suppress non-lighting of the end portion, the pigment composition of the present invention preferably has a dot-like, linear and / or planar contact portion between the (a) component and the (b) component. Specific examples of dot-like and / or linear contact portions include secondary particles formed by agglomeration of primary particles of the (a) component and primary particles of the (b) component in contact with each other, tertiary or higher order aggregates formed by further agglomeration of the secondary particles, tertiary or higher order aggregates formed by agglomeration of secondary particles consisting only of the (a) component and secondary particles consisting only of the (b) component, and a mixture of these. Specific examples of planar contact portions include a form in which at least a part of the surface of the (a) component is covered with the (b) component, and a form in which at least a part of the surface of the (b) component is covered with the (a) component.

[0099] The principle by which the above-mentioned components (a) and (b) come into contact is not particularly limited, but it is preferable that the contact is due to a strong adsorption form between the planar skeletons of the component (a) and the phthalocyanine skeleton of the component (b) that originates from the π-π interaction. Such a strong adsorption form can be obtained by making the components (a) and (b) coexist and producing the pigment composition of the present invention by the solvent salt milling method described below.

[0100] In order to suppress non-lighting of the edges, the pigment composition of the present invention preferably further contains (c) a pigment having a benzimidazole skeleton and a perylene skeleton in the molecule (hereinafter, sometimes referred to as "component (c)"). The benzimidazole skeleton here means a structure represented by formula (38). Like component (a), component (c) imparts light-shielding properties to the pixel division layer, and also has the effect of further improving the effect of component (b) in suppressing non-lighting of the edges. Component (c) is a pigment that exhibits a dark purple color.

[0101] [ka]

[0102] Examples of the component (c) include a pigment represented by the formula (39) and a pigment represented by the formula (40).

[0103] [ka]

[0104] In formula (39) and formula (40), R 53 , R 54 , R 55 , R 56 , R 57 , R 58 , R 59 , R 60 , R 61 , R 62 , R 63 , R 64 , R 65 , R 66 , R 67 and R 68 each independently represents a hydrogen atom, a bromine atom, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms. Among them, the pigment represented by formula (41) and the pigment represented by formula (42) are preferred because they are excellent in further improving the effect of component (b) in suppressing non-lighting at the ends. There are no particular limitations on the method for synthesizing component (c), but for example, the method described in Patent Document 1 can be referenced.

[0105] [ka]

[0106] When the pigment composition of the present invention does not contain the later-described component (c), the content of the component (a) is preferably 80.0000 parts by mass or more, more preferably 85.0000 parts by mass or more, and even more preferably 90.0000 parts by mass or more, per 100.0000 parts by mass of the total of the components (a) and (b) in order to improve halftone processability. In order to suppress non-lighting at the end, the content is preferably 99.9999 parts by mass or less, more preferably 99.9900 parts by mass or less, and even more preferably 99.0000 parts by mass or less.

[0107] On the other hand, when the pigment composition of the present invention contains the component (c), the total content of the components (a) and (c) is preferably 80.0000 parts by mass or more, more preferably 85.0000 parts by mass or more, and even more preferably 90.0000 parts by mass or more, per 100.0000 parts by mass of the total of the components (a), (b), and (c), in order to improve halftone processability. In order to suppress non-lighting at the end, the total content is preferably 99.9999 parts by mass or less, more preferably 99.9900 parts by mass or less, and even more preferably 99.0000 parts by mass or less.

[0108] When the pigment composition of the present invention does not contain the component (c) described below, the content of the component (b) is preferably 0.0001 parts by mass or more, more preferably 0.0100 parts by mass or more, and even more preferably 1.0000 parts by mass or more, per 100.0000 parts by mass of the total of the components (a) and (b), in order to suppress non-lighting of the end portions. In order to improve halftone processability, the content is preferably 20.0000 parts by mass or less, more preferably 15.0000 parts by mass or less, and even more preferably 10.0000 parts by mass or less.

[0109] When the pigment composition of the present invention contains the (c) component, the content of the (b) component is preferably 0.0001 parts by mass or more, more preferably 0.0100 parts by mass or more, and even more preferably 1.0000 parts by mass or more, relative to 100.0000 parts by mass of the total of the (a), (b) and (c) components, in order to suppress non-lighting at the ends. In order to improve halftone processability, the content is preferably 20.0000 parts by mass or less, more preferably 15.0000 parts by mass or less, and even more preferably 10.0000 parts by mass or less.

[0110] In addition, the total content of components (a), (b) and (c) is preferably 80.0000 to 100.0000 parts by mass per 100.0000 parts by mass of the solid content of the pigment composition, in order to improve the light-blocking properties and halftone processability per mass of the solid content of the pigment composition and to suppress non-lighting of edges.

[0111] When the pigment composition of the present invention contains component (c), the content ratio of component (a) to component (c) is preferably component (a):component (c)=10:90 to 90:10 by mass, and more preferably 40:60 to 85:15, in order to achieve both suppression of non-lighting at edges and halftone processability.

[0112] The pigment composition of the present invention may further contain a (d) resin. In order to further improve the effect of component (b) in suppressing non-lighting at the ends, it is preferable that the (d) resin contains a resin having a repeating unit represented by formula (43) and / or a resin having a repeating unit represented by formula (44). That is, it is preferable that the pigment composition of the present invention further contains a (d) resin, and that the (d) resin contains a resin having a repeating unit represented by formula (43) and / or a resin having a repeating unit represented by formula (44).

[0113] [ka]

[0114] In formula (43), R 69represents a phenyl group substituted with one hydroxyl group, an unsubstituted phenyl group, or a hydrogen atom. p is an integer of 0 to 2. * represents a bonding site.

[0115] [ka]

[0116] In formula (44), R 70 R represents a hydrogen atom or a methyl group. 71 represents a single bond or a -COO- group. * represents a bonding site.

[0117] The resin having the repeating unit represented by formula (43) is obtained by reacting phenols with aldehydes under an acid catalyst. Examples of phenols include phenol, o-cresol, m-cresol, p-cresol, 2,3-dimethylphenol, 2,4-dimethylphenol, 2,5-dimethylphenol, and 2,6-dimethylphenol. Examples of aldehydes include paraformaldehyde, benzaldehyde, and hydroxybenzaldehyde. Examples of commercially available products include TR4020G, TR4080G, TR4000B, TR40B40G, TRM30B20G, and TRR5010G (all manufactured by Asahi Organic Chemicals Co., Ltd.).

[0118] The resin having the repeating unit represented by formula (44) can be obtained, for example, by radically polymerizing p-hydroxystyrene and / or 4-hydroxyphenyl (meth)acrylate, which are radical polymerizable monomers, in the presence of a thermal polymerization initiator. In addition, other monomer components such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, benzyl (meth)acrylate, isostearyl (meth)acrylate, diethylene glycol monomethyl ether (meth)acrylate, diethylene glycol monoethyl ether (meth)acrylate, triethylene glycol monomethyl ether (meth)acrylate, triethylene glycol monoethyl ether (meth)acrylate, and (meth)acrylic acid may be added and copolymerized. Commercially available products include VP-2500, VP-3500, and VP-8000 (all manufactured by Nippon Soda Co., Ltd.).

[0119] As the other (d) resin, an epoxy resin may be contained. The epoxy resin is preferably a solid at atmospheric pressure / 25° C., and examples thereof include epoxy resins having a biphenyl skeleton such as NC-3000 and NC-3000L, epoxy resins having an alicyclic skeleton such as XD-1000, XD-1000-2L, and XD-1000-H (all manufactured by Nippon Kayaku Co., Ltd.), and epoxy resins having a bisarylfluorene skeleton such as OGSOL PG-100 and CG-500 (all manufactured by Osaka Gas Chemicals Co., Ltd.).

[0120] In order to suppress non-lighting at the ends, the weight average molecular weight (Mw) of the (d) resin is preferably 2000 to 20000. In addition, in order to suppress non-lighting at the ends, the content of the (d) resin is preferably 1.0000 to 10.0000 parts by mass per 100.0000 parts by mass of the total of the (a) component and the (c) component.

[0121] The pigment composition of the present invention may contain (e) an organic solvent (hereinafter sometimes referred to as "component (e)") and / or water. Examples of component (e) include ethylene glycol monomethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol mono-n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol mono-n-propyl ether, diethylene glycol mono-n-butyl ether, propylene glycol monomethyl ether (hereinafter "PGME"), propylene glycol monoethyl ether, propylene glycol mono-n-propyl ether, propylene glycol mono-n-butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ... Examples of the monomer units include ethylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monoethyl ether, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, methyl lactate, ethyl lactate, 3-methoxybutyl acetate, methyl ethyl ketone, γ-butyrolactone (hereinafter, “GBL”), γ-valerolactone, N-methylpyrrolidone (hereinafter, “NMP”), o-dichlorobenzene, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate.

[0122] The pigment composition of the present invention may further contain other pigments other than the (a), (b) and (c) components, if necessary, for the purpose of adjusting the spectral reflectance spectrum of the pixel division layer. Examples of other pigments include organic orange pigments such as CI Pigment Orange 13, 36, 43, 60, 61, 62, 64, 71 and 72, organic red pigments such as CI Pigment Red 122, 123, 149, 178, 177, 179, 180, 189, 190, 202, 209, 254, 255 and 264, organic blue pigments such as CI Pigment Blue 16, 25, 56, 57, 60, 61, 64, 65, 66, 75, 79 and 80, and organic purple pigments such as CI Pigment Violet 19, 29 and 32. CI here means color index.

[0123] The pigment composition of the present invention may be in the form of a wet cake, fine powder or granules at 25°C / atmospheric pressure. The pigment composition of the present invention has a solid content of 70 to 100% by mass, and preferably has a solid content of 90 to 100% by mass in order to easily control the particle size distribution during the production of a pigment dispersion liquid described later. 10.0 g of the pigment composition is heated at 120°C for 2 hours under atmospheric pressure, and the mass (g) of the residue is measured, divided by the mass of the pigment composition before heating (10.0), multiplied by 100, and rounded off to one decimal place, to obtain the solid content (mass%) of the pigment composition.

[0124] The average primary particle diameter of the pigment composition of the present invention is preferably 10 nm or more, more preferably 20 nm or more, in order to improve halftone processability. From the same viewpoint, it is preferably 100 nm or less, more preferably 80 nm or less. The average primary particle diameter here refers to the number average value of the primary particle diameter calculated by a particle size measurement method using an image analysis type particle size distribution measuring device. A TEM can be used to take an image, and the average primary particle diameter can be calculated by analyzing 50 primary particles randomly selected from an image in which 100 or more primary particles are taken under a magnification condition of 50,000 times. If the particles are not spherical, the primary particle diameter (nm) is determined by rounding the average value of the major axis to the nearest tenth. For image analysis, image analysis type particle size distribution software Mac-View (manufactured by Mountec Co., Ltd.; JIS8827-1 compliant; particle size analysis-image analysis method) can be used.

[0125] The average aspect ratio of the pigment composition of the present invention is preferably 1.0 or more, more preferably 1.3 or more, in order to improve halftone processability. From the same viewpoint, it is preferably 3.0 or less, more preferably 2.5 or less. The average aspect ratio here means a value obtained by measuring the major axis and minor axis of each of the primary particles observed in the TEM image for each of the 50 primary particles randomly selected to calculate the average primary particle diameter, dividing the major axis by the minor axis, and rounding off the first decimal place.

[0126] The chemical structures of the compounds belonging to the components (a), (b), (c) and (d) of the present invention can be analyzed by combining known analytical techniques such as time-of-flight secondary ion mass spectrometry (TOF-SIMS), time-of-flight mass spectrometry (TOF-MS), liquid chromatography mass spectrometry (LC-MS), gas chromatography mass spectrometry (GC-MS), X-ray fluorescence spectrometry (XRF), inductively coupled plasma mass spectrometry (ICP-MS) and powder X-ray diffraction, using the pigment composition of the present invention as an analytical sample. In particular, the components corresponding to fine powders among the primary particle size distributions of the components (a), (b) and (c) have low crystallinity and may be slightly soluble in amide-based organic solvents such as dimethylformamide and N-methylpyrrolidone. The pigment composition may be added to an amide-based organic solvent, the stirred slurry is centrifuged, and the supernatant liquid sampled may be used as the analytical sample.

[0127] The contact area between the (a) and (b) components and the contact area between the (c) and (b) components can be detected by observing the difference in hue of each component using an optical microscope, or by using the aforementioned TOF-SIMS, or by using a micro-infrared spectrophotometer (μ-FT-IR). A transmission electron microscope (TEM) may also be used in combination. When observing a microscopic portion using a TEM, a sample is prepared by embedding the pigment composition in a two-component curing transparent resin without applying mechanical shearing, and the sample is processed into a thin piece with a thickness of 100 nm using a focused ion beam processing device (FIB), and the cross section is observed. Element mapping using TEM-EDX (energy dispersive X-ray spectroscopy) may also be used.

[0128] The method for producing the pigment composition of the present invention is not particularly limited, but for example, the following solvent salt milling method can be preferably applied. By the solvent salt milling method, primary particles and / or secondary particles of component (b) can be incorporated uniformly without uneven distribution in higher-order aggregates of component (a) or higher-order aggregates of components (a) and (c) when viewed macroscopically, and even if the amount of component (b) is small, the effect of suppressing non-lighting at the ends can be enhanced.

[0129] The (a) component, the (b) component, the water-soluble grinding material, and the water-soluble organic solvent are mixed, and the mixture is ground in a high-viscosity paste form at preferably 20 to 100°C, more preferably 40 to 90°C, for 5 to 10 hours using a wet kneader, so that at least a part of the (b) component is adsorbed on at least a part of the surface of the (a) component, while reducing the average primary particle size of the (a) component and the (b) component. Furthermore, the grinding process may be performed in the presence of the (c) component and / or the (d) resin. In order to maintain the hardness of the water-soluble grinding material high and improve the degree of fineness, it is desirable to heat the water-soluble grinding material, the (a) component, the (b) component, and the (c) component at 100 to 250°C for 30 minutes to 2 hours before the grinding process, thereby lowering the moisture content. The mixture is then poured into a large amount of water, preferably warm water, and stirred for 1 to 3 hours to obtain a pigment slurry. The water-soluble grinding material and the water-soluble organic solvent are washed and removed, and the residue is dried and then micronized by a dry grinding process so that the powder particle size D90 (hereinafter sometimes referred to as "powder particle size") based on volume is 3.0 to 20.0 μm, as measured by a laser diffraction particle size distribution measurement device, which has excellent measurement accuracy in the 1.0 μm or larger range, to obtain the pigment composition of the present invention. D90 means the particle size (nm) corresponding to 90% cumulatively from the small particle size side (0%) on the cumulative particle size distribution curve to the large particle size side. (b) The component is -SO 3 When the pigment has a H group, the proton dissociates due to the moisture remaining in the pigment composition, forming -SO 3 - It may be a group.

[0130] As the wet kneader, for example, a Kneader (manufactured by Inoue Seisakusho Co., Ltd.) can be used. As the water-soluble grinding material, a fine water-soluble inorganic salt having an average primary particle size of 0.1 to 50.0 μm is preferable, and examples thereof include sodium chloride, potassium chloride, and potassium sulfate (all of which are manufactured by Ako Kasei Co., Ltd.). As the water-soluble organic solvent, a glycol-based solvent is preferable. Examples of the glycol-based solvent include ethylene glycol, propylene glycol, diethylene glycol, and dipropylene glycol.

[0131] Other methods include, for example, the following. Component (a), a water-soluble grinding agent, and a water-soluble organic solvent are mixed, and the mixture is ground in a high-viscosity paste form using a wet kneader at preferably 20 to 100°C, more preferably 40 to 90°C, for 5 to 10 hours to reduce the average primary particle size of component (a). Furthermore, component (c) and / or resin (d) may be coexisted in the grinding process. Next, the mixture is poured into a large amount of water, preferably warm water, and stirred for 1 to 3 hours to obtain a pigment slurry. A mixed liquid in which component (b) is dissolved in a strong alkaline aqueous solution is added to the pigment slurry and stirred, and then a strong acid aqueous solution is gradually dropped to neutralize, and at least a part of the surface of component (a), or at least a part of the surfaces of component (a) and component (c), is coated with the precipitated component (b). As the alkaline aqueous solution, for example, a 5 to 30% by mass aqueous sodium hydroxide solution can be used. As the strong acid aqueous solution, for example, a 5 to 30% by mass aqueous hydrochloric acid solution can be used. The water-soluble grinding agent and the water-soluble organic solvent are washed and removed, and the residue is dried and then pulverized by dry grinding to a powder particle size of 3.0 to 20.0 μm to obtain the pigment composition of the present invention.

[0132] Also, a method of coating with the (d) resin by carrying out the same operation using a mixed solution prepared by dissolving the (d) resin in a strong alkaline aqueous solution instead of the mixed solution prepared by dissolving the (b) component in a strong alkaline aqueous solution described above can be preferably mentioned.

[0133] Another method for producing the pigment composition of the present invention includes a method including a step of compounding components (a) and (b) using a dry particle compounding device "Nobilta" (registered trademark) NOB-130 (manufactured by Hosokawa Micron Corporation).

[0134] The second aspect of the present invention is a photosensitive composition that contains, in addition to the pigment composition of the present invention, a (d) resin, a (e) organic solvent, and a (f) photosensitizer (hereinafter sometimes referred to as "component (f)"). The (d) resin and the (e) organic solvent are components common to the first aspect.

[0135] The resin (d) in the second embodiment functions as a binder for dispersing the pigment composition of the present invention in the pixel dividing layer and the spacer layer and for fixing it to the surface of the glass, the planarizing layer and / or the electrode.

[0136] Examples of the (d) resin include an alkali-soluble polyimide precursor, an alkali-soluble polyimide resin, an alkali-soluble polybenzoxazole precursor, an alkali-soluble siloxane resin, an alkali-soluble epoxy acrylate resin, an alkali-soluble maleimide resin, etc. The alkali-soluble resin here means a resin having a repeating unit having a carboxyl group and / or a hydroxyl group and having a weight average molecular weight (Mw) of 1,000 to 100,000.

[0137] The component (e) in the second embodiment is a dispersion medium for dispersing the pigment composition of the present invention and has the effect of improving the coatability of the photosensitive composition. As the component (e), the same solvent as in the first embodiment can be preferably used.

[0138] The photosensitive composition of the present invention has either negative photosensitivity or positive photosensitivity. It may have a negative photosensitivity, which is formed by pattern exposure to exposure light containing at least near ultraviolet light through an exposure mask having a transparent portion and a shielding portion, and by making the alkaline solubility of the film in the exposed portion relatively lower than that of the film in the unexposed portion, the film in the unexposed portion is removed with an alkaline developer. Alternatively, it may have a positive photosensitivity, which is formed by pattern exposure to exposure light containing at least near ultraviolet light through an exposure mask having a transparent portion and a shielding portion, and by making the alkaline solubility of the film in the exposed portion relatively higher than that of the film in the unexposed portion, the film in the exposed portion is removed with an alkaline developer.

[0139] When the photosensitive composition of the present invention has negative photosensitivity, the component (f) means a compound having two or more radical polymerizable groups in the molecule, and a photopolymerization initiator. Both components are exposed to exposure light and photocured by radical polymerization reaction to reduce the alkali solubility of the film in the exposed area, making it possible to form a pattern by negative photolithography. Examples of the radical polymerizable group include a vinyl group, an acryloxy group, and a methacryloxy group. Examples of the photopolymerization initiator include an oxime ester-based photopolymerization initiator.

[0140] When the photosensitive composition of the present invention has positive photosensitivity, the component (f) refers to a photoacid generator. The photoacid generator is exposed to exposure light and changes its chemical structure to generate an acid, which increases the alkali solubility of the film in the exposed area, making it possible to form a pattern by positive photolithography. Preferred examples of the acid generated include carboxylic acids and sulfonic acids.

[0141] In halftone processing using a halftone exposure mask having fully transparent portions, semi-transparent portions, and shielding portions within its plane, it is preferable that component (f) contains a photoacid generator and has positive photosensitivity, in order to achieve excellent in-plane uniformity in the opening widths of the multiple openings arranged in the pixel division layer. That is, the photosensitive composition of the present invention is preferably a photosensitive composition in which the component (f) contains a photoacid generator and has positive photosensitivity.

[0142] Examples of photoacid generators include naphthoquinone diazide compounds, oxime sulfonate compounds, and imide sulfonate compounds. Among them, naphthoquinone diazide compounds are preferred because they exhibit excellent dissolution suppression effects on the unexposed film, can increase the difference in alkali dissolution rate between the exposed and unexposed parts, and have excellent exposure sensitivity to exposure light including i-rays (wavelength 365 nm).

[0143] Preferred examples of the naphthoquinone diazide compound include a 4-naphthoquinone diazide sulfonyl ester compound obtained by reacting a compound having two or more phenolic hydroxyl groups in the molecule with 1,2-naphthoquinone-2-diazide-4-sulfonyl chloride, and a 5-naphthoquinone diazide sulfonyl ester compound obtained by reacting a compound having two or more phenolic hydroxyl groups in the molecule with 1,2-naphthoquinone-2-diazide-5-sulfonyl chloride.

[0144] A specific example of the component (f) is a 5-naphthoquinone diazide sulfonyl ester compound represented by formula (45).

[0145] [ka]

[0146] In formula (45), each Q independently represents a hydrogen atom or a group represented by formula (46), provided that at least one Q in one molecule is a group represented by formula (46).

[0147] [ka]

[0148] In formula (46), * represents a bonding site with an oxygen atom.

[0149] Commercially available products of component (f) include PA-28 (manufactured by Daito ChemiX Co., Ltd.), which is a naphthoquinone diazide compound that generates acid when exposed to i-rays, PAG103 and PAG203 (all manufactured by BASF), which are oxime sulfonate compounds that generate acid when exposed to i-rays, and NIT, NIN, and ILP-110 (all manufactured by Heraeus), which are imide sulfonate compounds that generate acid when exposed to i-rays.

[0150] The photosensitive composition of the present invention preferably contains at least one kind selected from the group of perylene dye derivatives described in Patent Document 1, in order to increase the in-plane uniformity of the opening width of the openings of the pixel dividing layer and the exposure sensitivity, and to suppress a decrease in the exposure sensitivity after storage of the photosensitive composition.

[0151] For the purpose of adjusting the spectral reflectance spectrum of the pixel dividing layer, the photosensitive composition of the present invention may contain a compound that does not have a maximum absorption wavelength in the wavelength region of 350 to 500 nm before heating but is converted by heating into a compound that has a maximum absorption wavelength in the wavelength region of 350 to 500 nm in the wavelength region of 350 to 780 nm described in Patent Document 1.

[0152] An example of a method for preparing the photosensitive composition of the present invention is a method in which a pigment dispersion containing the pigment composition of the present invention, the resin (d), and the component (e) is prepared in advance by wet media dispersion treatment using a bead mill in which ceramic beads are filled in a vessel, and then the pigment dispersion is added to a mixed liquid of the components (e) and (f), followed by stirring and, if necessary, filtering through a filter.

[0153] The particle size distribution D90 (cumulative 90% particle size) of the particle components in the photosensitive composition based on the light scattering intensity measured by dynamic light scattering is preferably 150 nm or more in order to improve storage stability, while it is preferably 300 nm or less in order to improve halftone processability. D90 refers to the value measured for a particle size distribution measurement sample. The particle size distribution measurement sample refers to a measurement object obtained by mixing equal amounts of dilution solvent into the photosensitive composition three times so that the photosensitive composition:dilution solvent = 1:99 (mass ratio) and stirring on a shaker for 10 minutes. The dilution solvent is an organic solvent having the same composition as the component (e) contained in the photosensitive composition. The particle size distribution here can be measured using a particle size distribution measurement device SZ-100 (manufactured by Horiba, Ltd.) using a dynamic light scattering method. D90 refers to the particle size (nm) that corresponds to 90% of the cumulative particle size distribution curve, starting from the small particle size side (0%) and accumulating toward the large particle size side.

[0154] The third aspect of the present invention is an organic EL display device having a pixel division layer and a spacer layer, the pixel division layer and the spacer layer containing a cured product of the photosensitive composition of the present invention. The cured product of the photosensitive composition here means a product obtained by a process of heating the photosensitive composition at atmospheric pressure at an actual temperature of 200°C to 400°C for 10 minutes or more. Other components may be contained within a range that does not impair the technical effect of the present invention. Examples of other components include adsorbed water. The total amount of other components is preferably 1.0000 parts by mass or less in 100.0000 parts by mass of the pixel division layer and the spacer layer.

[0155] The optical density of the pixel division layer per 1.0 μm of film thickness is preferably 0.7 or more in order to suppress external light reflection and increase the value of the display device, and is preferably 1.3 or less in terms of halftone processability.

[0156] The optical density can be measured by forming a pixel division layer on a transparent substrate and using an optical densitometer X-Rite 361T (manufactured by X-Rite). The higher the optical density, the higher the light blocking property. As the transparent base material, a transparent glass substrate "Tempax (manufactured by AGC Technoglass Co., Ltd.)" can be used.

[0157] The organic EL display device of the present invention has an advantageous effect of suppressing non-illumination of the light-emitting pixels arranged at the end of the substrate when forming the pixel division layer and the spacer layer, even if the pixel division layer and the spacer layer formed collectively by halftone processing have a large thickness. In addition, as described above, the organic EL display device has a feature that it is economically advantageous due to the collective formation by halftone processing. As an embodiment, for example, an organic EL display device having a substrate, a first electrode, a pixel division layer, a spacer layer, a light-emitting pixel, and a second electrode may be included. Furthermore, a planarization layer may be included. More specifically, the configuration of the organic EL display device shown in FIG. 2 of Patent Document 1 may be included.

[0158] A method for forming the pixel division layer and the spacer layer collectively is preferably a method including a coating step of coating a photosensitive composition to obtain a coating film, a pre-bake step of heating the coating film to obtain a pre-baked film, an exposure step of pattern-exposing the film to exposure light containing at least near-ultraviolet light through a half-tone exposure mask to obtain an exposed film having an exposed portion, a semi-exposed portion, and an unexposed portion within its surface, a development step of developing the film using an alkaline developer to obtain a developed film, and a curing step of thermally curing the film by heating to obtain a cured film.

[0159] As a coating device used in the coating step, a spin coater or a slit coater is preferably used because of its excellent thin film coating ability. After coating, pin gap pre-bake or contact pre-bake may be performed.

[0160] In the pre-baking step, the pre-baking temperature is preferably 50 to 150° C., and the pre-baking time is preferably 30 seconds to 5 minutes. The thickness of the pre-baked film is preferably 5.0 to 10.0 μm.

[0161] Examples of the exposure device used in the exposure step include a stepper, a mirror projection mask aligner (MPA), and a parallel light mask aligner (PLA). The near ultraviolet light irradiated during exposure is preferably the j-line (wavelength 313 nm) or i-line (wavelength 365 nm) of an ultra-high pressure mercury lamp, and more preferably the h-line (wavelength 405 nm) or a mixed line including the h-line and the g-line (wavelength 436 nm). The halftone exposure mask has a full transmission part, a semi-transmission part, and a shielding part in the substrate plane, and is preferably designed so that the exposure amount in the semi-transmission part is 10 to 50% when the exposure amount in the full transmission part is 100% and the exposure amount in the shielding part is 0%. The exposed part in the exposed film means a part that is pattern-exposed through the full transmission part of the exposure mask, the semi-exposed part means a part that is pattern-exposed through the semi-transmission part of the exposure mask, and the unexposed part means a part that is not exposed by the shielding part of the exposure mask. The difference in dissolution rate per unit time of exposed, semi-exposed and unexposed areas in an alkaline developer due to the difference in the amount of exposure on the same surface makes it possible to form a pixel division layer and a spacer layer all at once by halftone processing.

[0162] Examples of the developing method in the developing step include shower, dipping, and paddle methods, and a method in which the exposed film is immersed for 10 seconds to 3 minutes is included. The paddle method is preferred in terms of improving halftone processability. Examples of the alkaline developer include 0.4 to 2.5 mass% tetramethylammonium hydroxide aqueous solution (hereinafter referred to as "TMAH"), and 2.38 mass% TMAH is preferred. A washing process using a shower of deionized water and a water removal process using air jets may be added.

[0163] In the curing step, the developed film is thermally cured by heating, and the developer and moisture remaining in the film are evaporated to obtain a cured film. Examples of the heating device include a hot air oven and an IR oven, and the heating atmosphere is nitrogen or air. The heating temperature is preferably 200 to 350°C under atmospheric pressure, more preferably 220 to 280°C. EXAMPLES

[0164] The present invention will be described in detail below with reference to examples and comparative examples, but the aspects of the present invention are not limited to these. First, the evaluation methods used in the examples and comparative examples will be described.

[0165] <Measurement of the minimum required exposure (exposure sensitivity)> A silver alloy (an alloy consisting of 99.00 mass% silver and 1.00 mass% copper) was formed on the entire surface of an alkali-free glass substrate measuring 150 mm in length and 150 mm in width by a sputtering method. An ITO (indium-tin oxide) film was then formed on the entire surface by a sputtering method to obtain a glass substrate having a silver alloy film / ITO film on the entire surface of the alkali-free glass substrate.

[0166] The positive photosensitive compositions 1-20 obtained in Examples 1-15 and Comparative Examples 1-5 were applied to the ITO surface of a glass substrate having a silver alloy film / ITO film by using a spin coater, adjusting the rotation speed so that the thickness of the pixel division layer obtained after the curing process described later was 2.9-3.1 μm and the thickness of the spacer layer was 2.4 μm (i.e., the total thickness of the pixel division layer and the spacer layer was 5.3-5.5 μm), to obtain a coating film. Furthermore, the coating film was prebaked at 110° C. for 120 seconds under atmospheric pressure using a hot plate to obtain a prebaked film. Through a positive halftone exposure mask (a mask with an arrangement of 220 fully transparent squares of 30.0 μm in length and 30.0 μm in width, designed so that the exposure amount in the semi-transparent areas is 15% when the exposure amount in the fully transparent areas is 100% and the exposure amount in the shielding areas is 0%), the mask is exposed to 40 to 200 (mJ / cm) of light using a double-sided alignment single-sided exposure device. 2 The prebaked film was pattern-exposed to a mixture of g, h, and i rays from an ultra-high pressure mercury lamp, with the exposure amount changed stepwise in 10 mJ increments within the range of 10 mJ (i-ray equivalent value), to obtain an exposed film having exposed, semi-exposed, and unexposed areas within its surface. The pattern exposure was performed by contacting a positive half-tone exposure mask with the surface of the prebaked film.

[0167] Next, in the development process, development was performed by the paddle method using a small photolithography developing device (AD-1200; manufactured by Takizawa Sangyo Co., Ltd.) and 2.38 mass % TMAH, which is an alkaline developer. The paddle method here refers to a method in which the alkaline developer is shower-coated on the surface of the exposed film for 10 seconds, and then left to stand until a predetermined development time is reached, and development is performed. The development time was set to a range of 60 to 120 seconds, and the film loss (μm) in the development process was 0.8 μm. The film loss in the development process here refers to the value obtained by subtracting the total film thickness of the pixel division layer and the spacer layer after development from the film thickness of the pre-baked film. Furthermore, after rinsing with deionized water for 30 seconds by the shower method, the substrate was rotated at 200 rpm for 30 seconds and dried to obtain a developed film.

[0168] Next, as a curing step, the developed film was heated in air at 250°C for 1 hour using a high-temperature inert gas oven (INH-9CD-S; manufactured by Koyo Thermo Systems Co., Ltd.) to obtain a substrate for evaluating the required minimum exposure dose, which was provided with a pixel dividing layer and a spacer layer. For reference, FIG. 3 shows an image of a cross section of the substrate for evaluating the required minimum exposure dose obtained in Example 1, observed with a scanning electron microscope (SEM). In FIG. 3, 5 is the pixel dividing layer, and 6 is the spacer layer.

[0169] The openings of the pixel division layer were observed using an FPD inspection microscope (MX-61L; Olympus Corporation), and the minimum exposure value that was opened so that the average value of the openings at 10 openings in each exposure region was within the range of 30.0 ± 0.1 μm was determined as the minimum required exposure (mJ / cm 2 : i-ray equivalent value).

[0170] (1) Evaluation of the light-shielding properties (OD / μm) of the cured film For the substrates for evaluating light-shielding properties on which a cured film having a thickness of 3.0 μm was formed, an optical densitometer (X-Rite 361T, manufactured by X-Rite) was used to measure the total optical density (Total OD value) at three points on the film surface side, and the average value was calculated by averaging the values. The average value was further divided by 3.0, and the value was rounded off to the nearest tenth, which was taken as the OD value per 1.0 μm of film thickness, that is, the light-shielding property of the cured film (OD / μm). The evaluation was performed based on the criterion that the higher the light-shielding property, the better the cured film. The OD value of Tempax, which does not have a cured film formed thereon, was separately measured and found to be 0.00, so the total optical density of the substrates for evaluating light-shielding properties was considered to be the total optical density of the cured film. The thickness of the cured film was calculated by averaging the values ​​measured at three points on the surface using a stylus-type film thickness measuring device (Surfcom, Tokyo Seimitsu Co., Ltd.), and the average value was rounded off to the nearest tenth.

[0171] (2) Evaluation of organic EL display devices (number of non-illuminated pixels) The central and end portions of the organic EL display devices obtained in Examples 1 to 15 and Comparative Examples 1 to 5 were driven with a voltage of 4V, and 100 luminescent pixels arranged in the central portion and 100 luminescent pixels arranged in the end portions were each observed by magnifying them at 100 times on a monitor, and the number of pixels in which no light was observed, i.e., non-light-emitting pixels, was counted, and the organic EL display device was evaluated as being superior with fewer occurrences. Note that a luminescent pixel in which the non-light-emitting portion exceeded 50% of the 100% area of ​​the pixel was evaluated as a non-light-emitting pixel. The evaluation was based on the following criteria, with AA and A to C being pass, and D to E being fail. Only when both the light-emitting pixel arranged in the center and the light-emitting pixel arranged at the end were pass, the organic EL display device was judged as pass. When either one was fail, the organic EL display device was judged as fail. Note that, since the occurrence of dark spots (granular localized non-light-emitting portions arranged unevenly within a light-emitting pixel) was not observed in all the examples and comparative examples, it was possible to accurately count the number of non-illuminating pixels that occurred. AA: No unlit pixels are observed. A: One or two unlit pixels are observed. B: Three or four unlit pixels are observed. C: 5 to 9 unlit pixels are observed. D: 10 to 14 unlit pixels are observed. E: 15 or more unlit pixels are observed.

[0172] (Synthesis Example 1: Synthesis of triphenodioxazine pigment B) 1500.00 g of acetic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) was placed in a flask, and 500.00 g (2.42 mol) of 2,5-diamino-3,6-dichloro-1,4-benzoquinone (manufactured by Tokyo Chemical Industry Co., Ltd.) and 20.00 g of benzenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. The liquid temperature was maintained at 30° C. and the mixture was stirred for 10 hours to cause a reaction, thereby obtaining a compound represented by formula (47), which was then separated by filtration.

[0173] [ka]

[0174] Next, 5365.05 g of 1,3-dimethyl-2-imidazolidinone (Tokyo Chemical Industry Co., Ltd.) was placed in the flask, and 684.04 g (2.35 mol) of the intermediate represented by formula (47) and 1037.73g (4.94mol) of 3-amino-9-ethylcarbazole (Tokyo Chemical Industry Co., Ltd.) was added and stirred at a liquid temperature of 30°C for 30 minutes. Furthermore, 5.00g of triethylamine was added and stirred at a liquid temperature of 40°C for 7 hours to generate a triphenodioxazine precursor. Furthermore, 190.22g (1.00mol) of p-toluenesulfonic acid monohydrate (Tokyo Chemical Industry Co., Ltd.) was added as an oxidizing agent, the liquid temperature was raised to 180°C, and stirring was maintained for 6 hours to perform ring closure of the triphenodioxazine precursor, and a slurry containing a pigment crude was obtained, which was cooled to 50°C and filtered to obtain a wet cake. The wet cake was washed once with 1,3-dimethyl-2-imidazolidinone, washed twice with ethanol, and then washed with water and filtered three times to collect the filtrate. After drying for 48 hours in a vacuum dryer at 100° C., dry grinding was carried out using a Nano Jet Mizer (manufactured by Aisin Nano Technologies Co., Ltd.) to obtain triphenodioxazine pigment B represented by formula (48).

[0175] [ka]

[0176] (Synthesis Example 2: Synthesis of triphenodioxazine pigment C) 1500.00 g of pentanoic anhydride (manufactured by Tokyo Chemical Industry Co., Ltd.) was placed in a flask, and 505.73 g (2.42 mol) of 2,5-dichloro-3,6-dihydroxy-p-benzoquinone (manufactured by Tokyo Chemical Industry Co., Ltd.) and 20.00 g of benzenesulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. The liquid temperature was maintained at 30° C. and the mixture was stirred for 10 hours to cause a reaction, thereby obtaining a compound represented by formula (49), which was then separated by filtration.

[0177] [ka]

[0178] Next, 5365.05g of 1,3-dimethyl-2-imidazolidinone was placed in a flask, 886.44g (2.35mol) of the intermediate represented by formula (49) and 1037.73g (4.94mol) of 3-amino-9-ethylcarbazole were added, and the mixture was stirred at a liquid temperature of 30°C for 30 minutes. Furthermore, 5.00g of triethylamine was added and the mixture was stirred at a liquid temperature of 40°C for 7 hours to generate a triphenodioxazine precursor. Furthermore, 190.22g (1.00mol) of p-toluenesulfonic acid monohydrate was added as an oxidizing agent, the liquid temperature was raised to 180°C, and stirring was maintained for 6 hours to perform ring closure of the triphenodioxazine precursor, and a slurry containing a pigment crude was obtained, which was cooled to 50°C and filtered to obtain a wet cake. The wet cake was washed once with 1,3-dimethyl-2-imidazolidinone, twice with ethanol, and then washed with water and filtered three times to collect the residue. After drying for 48 hours in a vacuum dryer at 100°C, the residue was dry-pulverized using a Nanojetmizer (manufactured by Aisin Nano Technologies Co., Ltd.) to obtain triphenodioxazine pigment C represented by formula (50).

[0179] [ka]

[0180] (Synthesis Example 3: Synthesis of Dye B) Dye B, a perylene dye derivative, was synthesized by the following method based on Synthesis Example 9 of Patent Document 1.

[0181] 50.00g of CI Pigment Red 178 was dissolved in 500.00g of 80% by mass concentrated sulfuric acid, heated, and stirred at a liquid temperature of 70°C for 6 hours to allow the sulfonation reaction to proceed. The mixture was then poured into 5kg of ice water to obtain a slurry containing precipitates, which was then filtered. The filtered product was then washed with ethanol, and repeatedly washed with water until the residual amount of sulfate ions determined by IC fell below 50 ppm by mass, and dried at 80°C under reduced pressure for 24 hours. The product was then pulverized by a dry grinding process using a nanojet mister, and coarse particles were removed by passing the product through a stainless steel sieve filter (opening diameter 50μm), to obtain dye B, which is a mixture of the compound represented by formula (51): the compound represented by formula (52): the compound represented by formula (53) = a mass ratio of 25:65:10. The structure of dye B was analyzed by LC-MS and TOF-SIMS.

[0182] [ka]

[0183] (Synthesis Example 4: Synthesis of Polyimide Precursor B) Polyimide precursor B was synthesized by the following method based on Synthesis Examples 1 and 2 of Patent Document 1.

[0184] 18.3g (0.05mol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane was dissolved in 100mL of acetone and 17.4g (0.3mol) of propylene oxide, and cooled to -15℃. A solution of 0.11mol (20.4g) of 3-nitrobenzoyl chloride dissolved in 100mL of acetone was added dropwise to this. After the dropwise addition, the reaction was carried out at -15℃ for 4 hours, and then the temperature was returned to room temperature. The precipitated white solid was filtered and dried in vacuum at 50℃. 30g of the solid was placed in a 300mL stainless steel autoclave, dispersed in 250mL of methyl cellosolve, and 2g of 5% palladium-carbon was added. Hydrogen was introduced into this with a balloon, and the reduction reaction was carried out at room temperature. After about 2 hours, it was confirmed that the balloon did not shrink any more, and the reaction was terminated. After the reaction was completed, the catalyst palladium compound was removed by filtration, and the mixture was concentrated by a rotary evaporator to obtain a hydroxyl group-containing diamine compound A.

[0185] Under a dry nitrogen stream, 31.0 g (0.10 mol) of 3,3',4,4'-diphenylethertetracarboxylic dianhydride was dissolved in 500 g of NMP. 45.35 g (0.075 mol) of hydroxyl group-containing diamine compound A and 1.24 g (0.005 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane were added together with 50 g of NMP, and reacted at 20 ° C for 1 hour, and then reacted at 50 ° C for 2 hours. As a terminal blocking agent, 4.36 g (0.04 mol) of 4-aminophenol was added together with 5 g of NMP, and reacted at 50 ° C for 2 hours. Then, 28.6 g (0.24 mol) of N,N-dimethylformamide dimethylacetal was dropped. After the addition, the mixture was stirred at 50 ° C for 3 hours. After the stirring was completed, the solution was cooled to room temperature, and then the solution was added to 3 L of water to obtain a white precipitate. The above procedure was repeated five times to obtain a white precipitate, which was collected as a filter cake, washed five times with water, and then dried in a vacuum dryer at 80°C for 24 hours to obtain a polyimide precursor B. The weight-average molecular weight (Mw) of the polyimide precursor B was 25,000.

[0186] (Synthesis Example 5: Synthesis of quinone diazide compound a) A quinone diazide compound a was synthesized by the following method based on Synthesis Example 6 of Patent Document 1.

[0187] Under a dry nitrogen stream, 21.22 g (0.05 mol) of TrisP-PA (manufactured by Honshu Chemical Industry Co., Ltd.) and 36.27 g (0.135 mol) of 5-naphthoquinone diazide sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and brought to room temperature. A solution of 15.18 g of triethylamine dissolved in 50 g of 1,4-dioxane was added dropwise to the system so that the temperature was 35°C or less. After the dropwise addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered, and the filtrate was poured into water. Then, filtration was performed to collect the precipitate. The precipitate was dried in a vacuum dryer to obtain a quinone diazide compound a represented by formula (54).

[0188] [ka]

[0189] In formula (54), * represents a bonding site with an oxygen atom.

[0190] (Synthesis Example 6: Synthesis of quinone diazide compound b) A quinone diazide compound b was synthesized by the following method based on Synthesis Example 7 of Patent Document 1.

[0191] The same synthesis method as in Synthesis Example 5 was carried out except that 36.27 g (0.135 mol) of 4-naphthoquinone diazide sulfonyl chloride was used instead of 36.27 g (0.135 mol) of 5-naphthoquinone diazide sulfonyl chloride, to obtain quinone diazide compound b represented by formula (55).

[0192] [ka]

[0193] In formula (55), * represents a bonding site with an oxygen atom.

[0194] (Synthesis Example 7: Synthesis of Phthalocyanine Derivative A) 50.00 g of metal-free phthalocyanine (sublimation purified product, manufactured by Sigma-Aldrich) was added to 500.00 g of 10% by mass fuming sulfuric acid, and the mixture was stirred at a liquid temperature of 20°C for 1 hour, and then stirred at a liquid temperature of 40°C for 8 hours to allow the sulfonation reaction to proceed. The mixture was then poured into 5 kg of ice water to obtain a slurry containing a precipitate, which was then filtered. The filtered product was then washed with ethanol, and repeatedly washed with water until the residual amount of sulfate ions determined by IC fell below 50 ppm by mass, and dried at 80°C under reduced pressure for 24 hours. The product was then pulverized by a dry grinding process using a nanojet mister to obtain phthalocyanine derivative A, which is a mixture of the compound represented by formula (30): the compound represented by formula (31) in a mass ratio of 87:13. The structure of phthalocyanine derivative A was analyzed by LC-MS and TOF-SIMS. The amount of Cu atoms was determined by ICP-MS to be below the detection limit (less than 1 ppm by mass).

[0195] (Synthesis Example 8: Synthesis of Phthalocyanine Derivative B) 50.00 g of vanadyl phthalocyanine (sublimation purified product, manufactured by Sigma-Aldrich) was added to 500.00 g of 30% by mass fuming sulfuric acid and stirred at a liquid temperature of 60° C. for 6 hours to allow the sulfonation reaction to proceed. Thereafter, the same operations as in Synthesis Example 7 were carried out to obtain phthalocyanine derivative B, which is a mixture of the compound represented by formula (56): the compound represented by formula (57) in a mass ratio of 45:55. The structure of phthalocyanine derivative B was analyzed by LC-MS, TOF-SIMS, and XRF. The amount of Cu atoms was quantified by ICP-MS, and was found to be below the detection limit (less than 1 ppm by mass).

[0196] [ka]

[0197] (Synthesis Example 9: Synthesis of Phthalocyanine Derivative C) Phthalocyanine derivative C, which is a mixture of the compound represented by formula (58) and the compound represented by formula (59) in a mass ratio of 54:46, was obtained by the same method as in Synthesis Example 8, except that zinc phthalocyanine (sublimation purified product, manufactured by Sigma-Aldrich) was used instead of vanadyl phthalocyanine. The structure of phthalocyanine derivative C was analyzed by LC-MS, TOF-SIMS, and XRF. Cu atoms were quantified by ICP-MS, and found to be below the detection limit (less than 1 ppm by mass).

[0198] [ka]

[0199] (Synthesis Example 10: Synthesis of Phthalocyanine Derivative D) 100.00 g of zinc phthalocyanine (sublimation purified product, Sigma-Aldrich) was mixed with 203.70 g of bromine, 333.33 g of sulfuryl chloride, 51.85 g of sodium chloride, and 388.89 g of aluminum chloride, and heated at 140°C for 15 hours. Then, the mixture was poured into 10 kg of water, stirred for 1 hour, filtered, washed with water, and washed with ethanol to obtain a wet cake. The mixture was repeatedly washed with water and filtered five times, filtered, dried at 80°C under reduced pressure for 48 hours, and finely pulverized by dry grinding using a nanojet mister to obtain phthalocyanine derivative D represented by formula (37). The structure of phthalocyanine derivative D was analyzed by TOF-SIMS and XRF. The amount of Cu atoms was quantified by ICP-MS, and was below the detection limit (less than 1 mass ppm).

[0200] (Synthesis Example 11: Synthesis of Phthalocyanine Derivative E) 100.00 g of zinc phthalocyanine (sublimation purified product, Sigma-Aldrich) was mixed with 767.00 g of bromine, 303.00 g of sulfuryl chloride, 50.000 g of sodium chloride, and 363.00 g of aluminum chloride, and heated at 140° C. for 15 hours. The subsequent steps were carried out in the same manner as in Synthesis Example 10 to obtain phthalocyanine derivative E represented by formula (60). The structure of phthalocyanine derivative E was analyzed by TOF-SIMS and XRF. Cu atoms were quantified by ICP-MS, and the result was below the detection limit (less than 1 ppm by mass).

[0201] [ka]

[0202] (Synthesis Example 12: Synthesis of Phthalocyanine Derivative F) 4660.80g of chlorosulfonic acid and 1070.73g of thionyl chloride were mixed, and 576.40g of titanyl phthalocyanine (sublimation refined product, manufactured by Tokyo Chemical Industry Co., Ltd.) was added and dissolved. This solution was stirred for 20 hours at a liquid temperature of 20°C, poured into 3kg of ice water and stirred for 1 hour, filtered, washed with water, and a wet cake was obtained. 865.95g of 3-aminobenzenesulfonic acid and 666.67g of 30% by mass aqueous sodium hydroxide solution were added to 1kg of ice water, and the entire amount of the wet cake was further poured in and stirred for 3 hours at a liquid temperature of 5°C. The liquid temperature was further raised to 50°C and stirred for 3 hours, after which it was cooled to 20°C and 10% by mass aqueous hydrochloric acid solution was gradually added dropwise until the pH became 2. The precipitate was washed with water three times and filtered, dried at 80°C under reduced pressure for 48 hours, and then pulverized by a dry grinding process using a nanojetmizer to obtain phthalocyanine derivative F represented by formula (35). The structure of phthalocyanine derivative F was analyzed by LC-MS, TOF-SIMS, and XRF. Cu atoms were quantified by ICP-MS, and found to be below the detection limit (less than 1 ppm by mass).

[0203] (Synthesis Example 13: Synthesis of Phthalocyanine Derivative G) Phthalocyanine derivative G, which is a mixture of the compound represented by formula (32): the compound represented by formula (33) = mass ratio 95:5, was obtained in the same manner as in Synthesis Example 12, except that 514.55 g of metal-free phthalocyanine (sublimation purified product, manufactured by Sigma-Aldrich) was used instead of titanyl phthalocyanine (sublimation purified product, manufactured by Tokyo Chemical Industry Co., Ltd.) and 445.45 g of 3-aminopropionic acid was used instead of 3-aminobenzenesulfonic acid. The structure of phthalocyanine derivative G was analyzed by LC-MS and TOF-SIMS. The amount of Cu atoms was quantified by ICP-MS and was below the detection limit (less than 1 ppm by mass).

[0204] (Synthesis Example 14: Synthesis of phthalocyanine derivative H) Phthalocyanine derivative H, which is a mixture of the compound represented by formula (30) and the compound represented by formula (31) in a mass ratio of 81:19, was obtained in the same manner as in Synthesis Example 7, except that "Heliogen Blue" (registered trademark) D7490 (CI Pigment Blue 16, manufactured by BASF) was used instead of metal-free phthalocyanine (sublimation purified product, manufactured by Sigma-Aldrich). The structure of phthalocyanine derivative H was analyzed by LC-MS and TOF-SIMS. Cu atoms were quantified by ICP-MS, and found to be 24 ppm by mass.

[0205] (Synthesis Example 15: Synthesis of Phthalocyanine Derivative I) Phthalocyanine derivative I, which is a mixture of the compound represented by formula (30) and the compound represented by formula (31) in a mass ratio of 80:20, was obtained in the same manner as in Synthesis Example 7, except that CYANINE BLUE TS8135 (CI Pigment Blue 16, manufactured by Sanyo Dye Co., Ltd.) was used instead of metal-free phthalocyanine (sublimation purified product, manufactured by Sigma-Aldrich Co., Ltd.). The structure of phthalocyanine derivative I was analyzed by LC-MS and TOF-SIMS. Cu atoms were quantified by ICP-MS to find that they were 5029 ppm by mass.

[0206] (Synthesis Example 16: Synthesis of phthalocyanine derivative J) Phthalocyanine derivative J, which is a mixture of the compound represented by formula (61) and the compound represented by formula (62) in a mass ratio of 39:61, was obtained in the same manner as in Synthesis Example 8, except that copper phthalocyanine (sublimation purified product, manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of vanadyl phthalocyanine. The structure of phthalocyanine derivative J was analyzed by LC-MS, TOF-SIMS, and XRF. Cu atoms were quantified by ICP-MS to find that they were 90145 ppm by mass.

[0207] [ka]

[0208] Example 1 3000.00 g of "Cromophtal" (registered trademark) Violet D5700 (manufactured by BASF: CI Pigment Violet 37) was heated in an oven at 200°C for 1 hour under atmospheric pressure / air to obtain triphenodioxazine pigment A represented by formula (10).

[0209] 3000.00 g of “Spectrasense” (registered trademark) Black K0087 (manufactured by BASF) was heated in an oven at 250° C. for 1 hour under atmospheric pressure / air to obtain perylene pigment A, which is an isomer mixture of the compound represented by formula (41) and the compound represented by formula (42).

[0210] Next, pigment composition 1 was prepared by a solvent salt milling method. 225.00g of triphenodioxazine pigment A (component a), 25.00g of phthalocyanine derivative A (component b), 250.00g of perylene pigment A (component c), 2.5kg of water-soluble grinding agent (sodium chloride particles with an average primary particle diameter of 0.5μm, which had been heated at 230℃ for 1 hour to reduce the moisture content to 0.1% by mass), and 250.00g of dipropylene glycol were mixed and charged into a stainless steel 1-gallon kneader (manufactured by Inoue Seisakusho) and kneaded at 90℃ for 8 hours to obtain a dark purple kneaded product. This kneaded product was put into 5L of warm water, stirred for 1 hour while maintaining the temperature at 70℃ to form a slurry, and washed with deionized water and filtered three times to remove the water-soluble grinding agent and dipropylene glycol. The mixture was then dried in an oven at 100°C under atmospheric pressure / air for 6 hours, and then dry-pulverized using a ball mill to prepare Pigment Composition 1, which has an average primary particle size of 29 nm. Table 1 shows the blended masses of each raw material, the solid content, and the quantitative results of Cu atoms using ICP-MS.

[0211] [Table 1]

[0212] Next, pigment dispersion 1 was prepared using pigment composition 1 by the following method.

[0213] Into 900.00 g of mixed solvent (PGME: ethyl lactate: γ-butyrolactone = mass ratio 50: 40: 10) of component (e), 68.38 g of polyimide precursor B, which is a resin (d), was added and dissolved by stirring for 30 minutes. Furthermore, 4.59 g of dye B, which is a dye-type dispersant, was added and stirred for 30 minutes, and then pigment composition 1 was added and stirred for 30 minutes to obtain a preliminary stirring liquid. Next, the preliminary stirring liquid was sent to a vertical bead mill "Ultra Apex Mill Advance (registered trademark)" (manufactured by Hiroshima Metal & Machinery Co., Ltd.) in which 0.4 mmφ zirconia beads "Treceram (registered trademark)" (manufactured by Toray Industries, Inc.) were filled in the vessel at a filling rate of 75 volume %, and a wet media dispersion treatment was performed for 1 hour at a peripheral speed of 10 m / s by circulation method. The liquid was then sent to a vertical bead mill whose vessel was filled with 0.1 mmφ zirconia beads "Torayceram (registered trademark)" (manufactured by Toray Industries, Inc.) at a filling rate of 75% by volume, and a wet media dispersion process was carried out for 4 hours at a peripheral speed of 8 m / s using a circulation method, obtaining a pigment dispersion. A first filtration was carried out using a 0.8 μm diameter filter, and then a second filtration was carried out using a 0.2 μm diameter filter, preparing pigment dispersion 1. No change in solid content was observed before and after filtration. The blended masses of each raw material are shown in Table 2.

[0214] [Table 2]

[0215] Next, a positive photosensitive composition 1 was prepared using the pigment dispersion 1 by the following method.

[0216] Under yellow light, 0.48 g of polyimide precursor B, 0.57 g of quinone diazide compound a, 0.12 g of quinone diazide compound b, 0.54 g of 4,4',4"-trihydroxytriphenylmethane, 0.42 g of HMOM-TPHAP (manufactured by Honshu Chemical Industry Co., Ltd.) as a thermal crosslinking agent, and 0.04 g of a PGME solution of 5 mass % solids of BYK-333 (manufactured by BYK Japan Co., Ltd.) as a leveling agent were added to 9.14 g of a mixed solvent (PGME: ethyl lactate: γ-butyrolactone = mass ratio 50: 40: 10) as component (e), and the mixture was stirred for 30 minutes to dissolve. Furthermore, 38.70 g of pigment dispersion 1 was added and stirred for 30 minutes to prepare a positive photosensitive composition 1 with a solids content of 12 mass %. The blending masses of each raw material are shown in Table 3.

[0217] [Table 3]

[0218] The positive photosensitive composition 1 was applied to the surface of a transparent glass substrate "Tempax" (manufactured by AGC Technoglass Co., Ltd.) using a spin coater, adjusting the rotation speed so that the final thickness of the cured film would be 3.0 μm, to obtain a coating film. The coating film was prebaked at atmospheric pressure at 110° C. for 120 seconds using a hot plate (SCW-636; manufactured by Dainippon Screen Mfg. Co., Ltd.) to obtain a prebaked film. The g, h, and i mixed lines of an ultra-high pressure mercury lamp were determined by the method described above using a double-sided alignment single-sided exposure device. The entire surface of the prebaked film was irradiated with light at an exposure dose equivalent to 15% of the minimum required exposure dose to obtain an exposed film. Development, rinsing, and drying were performed in the same manner as in the measurement of the minimum required exposure dose to obtain a solid developed film. Using a high-temperature inert gas oven (INH-9CD-S; manufactured by Koyo Thermo Systems Co., Ltd.), the developed film was heated at 250°C in air for 1 hour to obtain a substrate for light-shielding evaluation having a solid cured film with a thickness of 3.0 μm, and the light-shielding property (OD / μm) of the cured film was evaluated by the method described above. The evaluation results are shown in Table 4.

[0219] [Table 4]

[0220] Furthermore, an organic EL display device having a pixel dividing layer and a spacer layer was produced using the positive photosensitive composition 1 by the following method.

[0221] FIG. 4 shows a process for producing an organic EL display device, including the steps of forming a pixel dividing layer and a spacer layer.

[0222] A silver alloy (an alloy consisting of 99.00 mass% silver and 1.00 mass% copper) was formed on the entire surface of the center 7 and end 8 of an alkali-free glass substrate having a length of 75 mm and a width of 150 mm by a sputtering method. An alkali-soluble novolac-based positive resist was used, and the substrate was immersed in a silver alloy etching solution having a liquid temperature of 30° C. and etched to obtain a patterned silver alloy film 9 having a thickness of 50 nm. Furthermore, an ITO film (indium-tin oxide) was formed on the entire surface by a sputtering method. An alkali-soluble novolac-based positive resist was used, and the substrate was immersed in a 5 mass% oxalic acid solution having a liquid temperature of 50° C. for 5 minutes, washed with deionized water for 2 minutes by shower water, and then dried by air blowing to obtain an ITO film 10 having a thickness of 10 nm and the same pattern. By the above process, a first electrode-forming substrate having a first electrode consisting of a laminated pattern of a silver alloy film / ITO film was obtained on the surface of the center 7 and end 8 of the alkali-free glass substrate.

[0223] The positive photosensitive composition 1 was applied to the surface of the first electrode-forming substrate using a spin coater, adjusting the rotation speed so that the thickness of the pixel division layer obtained after the curing process described below was 2.9 to 3.1 μm and the thickness of the spacer layer was 2.4 μm (i.e., the total thickness of the pixel division layer and the spacer layer was 5.3 to 5.5 μm), to obtain a coating film. Furthermore, the coating film was prebaked at 110° C. under atmospheric pressure for 120 seconds using a hot plate to obtain a prebaked film. A positive halftone exposure mask (a mask designed so that 100 square full transmission parts of length: 30.0 μm, width: 30.0 μm are arranged in two places, and the exposure amount in the semi-transmission part is 15% when the exposure amount in the full transmission part is 100% and the exposure amount in the shielding part is 0%) was used to pattern-expose the prebaked film 11 of the positive photosensitive composition 1 using a double-sided alignment single-sided exposure device at the minimum exposure amount required measured by the above-mentioned method to obtain an exposed film. The pattern exposure was performed by contacting a positive halftone exposure mask with the surface of the prebaked film. Then, development, rinsing and drying were performed in the same manner as in the measurement of the minimum required exposure dose to obtain a patterned developed film. The developed film was heated in air at 250°C for 1 hour using a high-temperature inert gas oven to obtain a pixel division layer-forming substrate in which a pixel division layer and a spacer layer 12 were formed on the surface of the center portion 7 and the surface of the end portion 8 of the first electrode-forming substrate.

[0224] Next, the organic EL layer 13 including the light-emitting layer is formed on the surface of the opening of the pixel division layer by vacuum deposition under a vacuum degree of 1×10 -3 Under deposition conditions of 0.1 Pa or less, the pixel division layer forming substrate was rotated with respect to the deposition source, and first, a compound (HT-1) represented by formula (63) was deposited to a thickness of 10 nm as a hole injection layer, and a compound (HT-2) represented by formula (64) was deposited to a thickness of 50 nm as a hole transport layer. Next, a compound (GH-1) represented by formula (65) was deposited to a thickness of 40 nm as a host material, and a compound (GD-1) represented by formula (66) was deposited to a thickness of 40 nm on the light emitting layer. Next, a compound (ET-1) represented by formula (67) and a compound (LiQ) represented by formula (68) were deposited to a thickness of 40 nm as an electron transport material in a volume ratio of 1:1.

[0225] [ka]

[0226] [ka]

[0227] Next, a compound (LiQ) was deposited to a thickness of 2 nm, and then a silver / magnesium alloy (volume ratio 10:1) was deposited to a thickness of 150 nm to form a second electrode 14. Next, under a low humidity / nitrogen atmosphere, a sealing layer 15 was formed using an epoxy resin adhesive, and a cap-shaped glass plate was attached to seal the substrate, obtaining an organic EL display device in which 100 green light-emitting pixels were arranged in the center and at the ends of the substrate. Note that each layer constituting the organic EL layer 13 is very thin compared to the pixel division layer described above, and a high measurement accuracy cannot be obtained using a stylus-type film thickness measurement device. Therefore, each layer was measured using a quartz crystal oscillation-type film thickness monitor suitable for thin films of less than 100 nm, and the value obtained by rounding off the first decimal place of the average value of three points in the substrate was used as the film thickness. Table 4 shows the results of evaluation of the prepared organic EL display device using the above-mentioned method.

[0228] (Examples 2 to 3) Pigment compositions 2 and 3 were prepared in the same manner as in Example 1, except that triphenodioxazine pigment B or triphenodioxazine pigment C was used instead of triphenodioxazine pigment A. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 1. Furthermore, pigment dispersions 2 to 3 and positive-type photosensitive compositions 2 to 3 were prepared in order using pigment compositions 2 to 3, respectively, and a substrate for evaluating light-shielding properties and an organic EL display device were produced in the same manner as in Example 1, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 2 and 3, and the evaluation results are shown in Table 4.

[0229] (Examples 4 to 5) Pigment compositions 4 to 5 were prepared in the same manner as in Example 1, except that phthalocyanine derivative H or phthalocyanine derivative I was used instead of phthalocyanine derivative A. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 1. Furthermore, pigment dispersions 4 to 5 and positive-type photosensitive compositions 4 to 5 were prepared in the same manner as in Example 1 using pigment compositions 4 to 5, respectively, and a substrate for evaluating light-shielding properties and an organic EL display device were fabricated, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 2 and 3, and the evaluation results are shown in Table 4.

[0230] Example 6 Pigment composition 6 was prepared in the same manner as in Example 1, except that perylene pigment A was not used, in the amounts shown in Table 5. Furthermore, pigment dispersion 6 and positive photosensitive composition 6 were prepared in this order using pigment composition 6 in the same manner as in Example 1, a substrate for evaluating light-shielding properties and an organic EL display device were produced, and the light-shielding properties of the cured film and the number of non-lighted pixels were evaluated. The blended masses of each raw material are shown in Tables 6 and 7, and the evaluation results are shown in Table 8.

[0231] [Table 5]

[0232] [Table 6]

[0233] [Table 7]

[0234] [Table 8]

[0235] (Examples 7 to 12) Pigment compositions 7 to 12 were prepared in the same manner as in Example 1, except that phthalocyanine derivative B, phthalocyanine derivative C, phthalocyanine derivative D, phthalocyanine derivative E, phthalocyanine derivative F, or phthalocyanine derivative G was used instead of phthalocyanine derivative A. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Tables 5 and 9. Furthermore, pigment dispersions 7 to 12 and positive-type photosensitive compositions 7 to 12 were prepared in the same manner as in Example 1 using pigment compositions 7 to 12, respectively, and a substrate for evaluating light-shielding properties and an organic EL display device were fabricated, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 6, 7, 10, and 11, and the evaluation results are shown in Tables 8 and 12.

[0236] [Table 9]

[0237] [Table 10]

[0238] [Table 11]

[0239] [Table 12]

[0240] (Example 13) 202.50g of triphenodioxazine pigment A, 22.50g of phthalocyanine derivative A, 225.00g of perylene pigment A, (d) 50.00g of TRR5010G (manufactured by Asahi Organic Chemicals Co., Ltd.), 2.5kg of water-soluble grinding material, and 250.00g of dipropylene glycol were mixed and charged into a stainless steel 1 gallon kneader (manufactured by Inoue Seisakusho Co., Ltd.) and kneaded at 90°C for 8 hours to obtain a dark purple kneaded product. This kneaded product was added to 5L of warm water, stirred for 1 hour while maintaining the temperature at 70°C to form a slurry, and washed with deionized water and filtered three times to remove the water-soluble grinding material and dipropylene glycol. Furthermore, it was dried in an oven at 100°C under atmospheric pressure / air for 6 hours, and then dry-milled using a ball mill to prepare pigment composition 13. The blended mass, average primary particle size, and quantitative results of Cu atoms for each raw material are shown in Table 9. 69 is a hydrogen atom, and p is 1, and the repeating unit is a cresol novolak resin (solid content 100% by mass) having a weight average molecular weight (Mw) of 10,000. The blended masses of each raw material and the quantitative results of Cu atoms are shown in Table 9. Furthermore, using pigment composition 13 in the same manner as in Example 1, pigment dispersion 13 and positive photosensitive composition 13 were prepared in this order, and a substrate for evaluating light-shielding properties and an organic EL display device were produced, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended masses of each raw material are shown in Tables 10 and 11, and the evaluation results are shown in Table 12.

[0241] Example 14 Pigment composition 14 was prepared in the same manner as in Example 13, except that VP-2500 (manufactured by Nippon Soda Co., Ltd.) was used instead of TRR5010G. VP-2500 is a compound represented by the formula (44), 70 is a hydrogen atom, and R 71The polyhydroxystyrene resin (solid content 100% by mass) has a repeating unit in which is a single bond, and has a weight average molecular weight (Mw) of 4200. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 9. Furthermore, using pigment composition 14 in the same manner as in Example 1, pigment dispersion 14 and positive photosensitive composition 14 were prepared in this order, and a substrate for evaluating light-shielding properties and an organic EL display device were produced, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 10 and 11, and the evaluation results are shown in Table 12.

[0242] Example 15 Pigment composition 15 was prepared in the same manner as in Example 13, except that VP-2500 was used instead of TRR5010G, and phthalocyanine derivative D was used instead of phthalocyanine derivative A. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 9. Furthermore, pigment dispersion 15 and positive photosensitive composition 15 were prepared in this order using pigment composition 15 in the same manner as in Example 1, and a substrate for evaluating light-shielding properties and an organic EL display device were produced, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 10 and 11, and the evaluation results are shown in Table 12.

[0243] Comparative Example 1 Pigment composition 16 was prepared in the same manner as in Example 1, except that phthalocyanine derivative J, which is a phthalocyanine derivative not belonging to the (b) component, was used instead of phthalocyanine derivative A. After preparation, the inside of the kneader was repeatedly washed using a mixed solution (N-methylpyrrolidone:deionized water = mass ratio 1:1) until the Cu atoms quantified by ICP-MS were below the lower detection limit, and then washed with deionized water and dried. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 13. Furthermore, using pigment composition 16 in the same manner as in Example 1, pigment dispersion 16 and positive photosensitive composition 16 were prepared in this order, and a substrate for evaluating light-shielding properties and an organic EL display device were produced, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended masses of each raw material are shown in Tables 14 and 15, and the evaluation results are shown in Table 16.

[0244] [Table 13]

[0245] [Table 14]

[0246] [Table 15]

[0247] [Table 16]

[0248] Comparative Example 2 Pigment composition 17 was prepared in the same manner as in Example 13, except that phthalocyanine derivative A was not used. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 13. Furthermore, pigment composition 17 was used in the same manner as in Example 1 to prepare pigment dispersion 17 and positive photosensitive composition 17 in that order, and a substrate for evaluating light-shielding properties and an organic EL display device were fabricated, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 14 and 15, and the evaluation results are shown in Table 16.

[0249] Comparative Example 3 Pigment composition 18 was prepared in the same manner as in Example 14, except that phthalocyanine derivative A was not used. The blended mass of each raw material, the average primary particle size, and the quantitative results of Cu atoms are shown in Table 13. Furthermore, pigment composition 18 was used in the same manner as in Example 1 to prepare pigment dispersion 18 and positive photosensitive composition 18 in that order, and a substrate for evaluating light-shielding properties and an organic EL display device were fabricated, and the light-shielding properties of the cured film and the number of non-lighting pixels were evaluated. The blended mass of each raw material is shown in Tables 14 and 15, and the evaluation results are shown in Table 16.

[0250] Comparative Example 4 A finely divided perylene black pigment 1 was produced by the following method based on Production Example 1 of Patent Document 1.

[0251] 500.00g of perylene pigment A obtained in Example 1 was mixed with 2.5kg of grinding material (same as that used in Example 1) and 250.00g of dipropylene glycol, and then charged into a stainless steel 1-gallon kneader and kneaded at 90°C for 8 hours. The kneaded product was added to 5L of warm water, and stirred for 1 hour while maintaining the temperature at 70°C to form a slurry. The grinding material and dipropylene glycol were removed by repeatedly filtering and washing with water until the chloride ion determined by ion chromatography was 50 mass ppm or less. Furthermore, the product was dried in an oven at 100°C under atmospheric pressure / air for 6 hours, and then the dried aggregates were loosened with a ball mill to obtain a finely divided perylene black pigment 1 having an average primary particle size of 25nm and consisting of an isomer mixture of a compound represented by formula (41) and a compound represented by formula (42).

[0252] Next, a finely divided dioxazine pigment 2 was produced by the following method based on Production Example 6 of Patent Document 1.

[0253] 500.00g of triphenodioxazine pigment A obtained in Example 1 was mixed with 2.5kg of grinding agent (same as that used in Example 1) and 250.00g of dipropylene glycol, and then charged into a stainless steel 1-gallon kneader and kneaded at 90°C for 5 hours. The kneaded product was added to 5L of warm water, and stirred for 1 hour while maintaining the temperature at 70°C to form a slurry, and then filtered and washed with water three times to remove the grinding agent and dipropylene glycol. Furthermore, the product was dried in an oven at 100°C under atmospheric pressure / air for 6 hours, and then the dried aggregates were loosened with a ball mill to obtain a finely divided dioxazine pigment 2 represented by formula (10) having an average primary particle diameter of 30nm.

[0254] 68.38g of polyimide precursor B was added to 900.00g of mixed solvent (PGME: ethyl lactate: γ-butyrolactone = mass ratio 50: 40: 10), and dissolved by stirring for 30 minutes. Furthermore, 4.59g of dye B was added, and after stirring for 30 minutes, 14.86g of finely divided perylene black pigment 1 and 12.16g of finely divided dioxazine pigment 2 were added and stirred for 30 minutes to obtain a preliminary stirring liquid. Next, the subsequent steps were performed in the same manner as in Example 1, and a pigment dispersion liquid 19 was obtained by performing a wet media dispersion treatment and filtration. Furthermore, positive-type photosensitive composition 19 was prepared using pigment composition 19 in the same manner as in Example 1, and a substrate for evaluating light-shielding property and an organic EL display device were produced, and the light-shielding property of the cured film and the number of non-illuminated pixels were evaluated. The blending masses of each raw material are shown in Tables 14 and 15, and the evaluation results are shown in Table 16.

[0255] Comparative Example 5 Pigment dispersion 20 was obtained by carrying out wet media dispersion treatment and filtration in the blending amounts shown in Table 14 in the same manner as in Comparative Example 4, except that the finely divided dioxazine pigment 2 was not used. Furthermore, a positive-type photosensitive composition 20 was prepared using the pigment composition 20 in the same manner as in Example 1, a substrate for evaluating light-shielding property and an organic EL display device were produced, and the light-shielding property of the cured film and the number of non-illuminated pixels were evaluated. The blending masses of each raw material are shown in Tables 14 and 15, and the evaluation results are shown in Table 16.

[0256] From the above results, it can be seen that in Examples 1 to 15, which used pigment compositions 1 to 15, the number of unlit edges was smaller than in Comparative Examples 1 to 3, which used pigment compositions 16 to 18, and Comparative Examples 4 and 5, which correspond to the prior art disclosed in Patent Document 1, and thus an excellent organic EL display device was obtained.

[0257] Although the mechanism behind the effect of suppressing non-illumination at the ends is unclear, it is thought that at least the effect of component (b) suppressing the increase in drive voltage required to light up the light-emitting pixels located at the ends contributes to this. Furthermore, when focusing particularly on the evaluation results of the organic EL display devices of Example 1, Examples 7 to 10, and Comparative Example 1, it can be seen that in solving this problem, not only the type of substituent that the phthalocyanine derivative has, but also the presence or absence of a central metal in the phthalocyanine skeleton and the selection of the type of the central metal are particularly important. Therefore, it is apparent that the pigment composition of the present invention is useful. [Industrial Applicability]

[0258] The pigment composition of the present invention can be preferably used for pixel division layers and spacer layers of organic EL display devices, TFT planarization layers of organic EL display devices, partition walls of quantum dot organic EL display devices (QD-OLED), planarization layers of micro LED displays, black matrices formed on the surface of color filter substrates of liquid crystal display devices or organic EL display devices, black column spacers of liquid crystal display devices, etc. Among these, the pigment composition can be particularly preferably used for pixel division layers and spacer layers provided in organic EL display devices that are required to be economically advantageous in addition to having high light-shielding properties. [Explanation of symbols]

[0259] 1: Central region of the substrate when forming the pixel division layer and spacer layer 2: Region of the edge of the substrate when forming the pixel division layer and the spacer layer 3: Central region of the substrate when forming the pixel division layer and spacer layer 4: Region of the edge of the substrate when forming the pixel division layer and the spacer layer 5: Pixel division layer 6: Spacer layer 7: Center of non-alkali glass substrate 8: Edge of non-alkali glass substrate 9: Silver alloy film 10: ITO film 11: Pre-baked film 12: Pixel division layer and spacer layer 13: Organic EL layer 14:Second electrode 15: Sealing layer

Claims

1. A pigment composition containing: (a) a pigment having an -NHCO- group and / or a -COO- group and a triphenodioxazine skeleton in the molecule; and (b) a compound represented by formula (1) and / or a compound represented by formula (2). 【Chemistry 1】 (In formula (1), -R 1 and -SO 2 NHR 2 R 3 represents a substituent bonded to a carbon atom constituting a benzene ring. 1 and m 2 are integers, each independently representing 0 to 2. 1 And 2 The sum of is 1 or 2. 1 Ha-SO 3 H or -SO 3 - Represents 2 represents a single bond or an alkylene group having 1 to 3 carbon atoms. 3 Ha-SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.) 【Chemistry 2】 (In formula (2), M represents V=O, Ti=O or Zn. -R 4 , -SO 2 NHR 5 R 6 , --Br and --Cl represent a substituent or an atom bonded to a carbon atom constituting a benzene ring. n 1 and n 2 are integers, each independently representing 0 to 2. 3 is an integer from 0 to 14. 4 is an integer from 0 to 5. n 1 and 2 and 3 and 4 The sum of n is 1 to 16, 1 and 2 The sum is 0 to 2. n 1 and 2 When the sum of is 0, M is Zn, and n 3 is 8 to 14. 4 Ha-SO 3 H or -SO 3 - Represents 5 represents a single bond or an alkylene group having 1 to 3 carbon atoms. 6 Ha-SO 3 H, -SO 3 - , -COOH and -COO - or -COOH, or -COO - Represents.)

2. The pigment composition according to claim 1, wherein the component (b) contains a compound represented by formula (28) and / or a compound represented by formula (29). 【Chemistry 3】 (In formula (28), -R 51 represents a substituent bonded to a carbon atom constituting a benzene ring. 3 is an integer, 1 or 2. 51 Ha-SO 3 H or -SO 3 - Represents.) 【Chemistry 4】 (In formula (29), -R 52 , -Br and -Cl represent a substituent or an atom bonded to a carbon atom constituting a benzene ring. 5 and 6 and 7 The sum of n is 1 to 16. 5 is an integer from 0 to 2. 6 is an integer from 0 to 14. 7 is an integer from 0 to 5. 5 When is 0, n 6 is 8 to 14. 52 Ha-SO 3 H or -SO 3 - Represents.)

3. 2. The pigment composition according to claim 1, wherein the content of Cu atoms in the solid content of the pigment composition as determined by inductively coupled plasma mass spectrometry (ICP-MS) is 100 ppm by mass or less.

4. The pigment composition according to claim 1 , further comprising (c) a pigment having a benzimidazole skeleton and a perylene skeleton in the molecule.

5. The pigment composition according to claim 1, further comprising a resin (d), the resin (d) comprising a resin having a repeating unit represented by formula (43) and / or a resin having a repeating unit represented by formula (44). 【Chemistry 5】 (In formula (43), R 69 represents a phenyl group substituted with one hydroxyl group, an unsubstituted phenyl group, or a hydrogen atom. p is an integer of 0 to 2. * represents a bonding site. 【Chemistry 6】 (In formula (44), R 70 represents a hydrogen atom or a methyl group. 71 represents a single bond or a -COO- group. * represents a bonding site.)

6. A photosensitive composition comprising the pigment composition according to any one of claims 1 to 5, (d) a resin, (e) an organic solvent, and (f) a photosensitizer.

7. 7. The photosensitive composition according to claim 6, wherein the component (f) contains a photoacid generator and has positive photosensitivity.

8. 7. An organic electroluminescence display device comprising a pixel dividing layer and a spacer layer, the pixel dividing layer and the spacer layer comprising a cured product of the photosensitive composition according to claim 6.

Citation Information

Patent Citations

  • Positive photosensitive pigment composition, cured film containing cured product thereof, and organic el display device

    WO2022270182A1

Cited By

  • Inspection apparatus and inspection method of semiconductor device

    CN122567662A